Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 0 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "Year 2015-2021" ] } The dataset includes 0 records from 10008 constituent datasets: 225 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 4 records from A taxonomic review of the genus Amicta Heylaerts, 1881 in North Africa, Near and Middle East (Lepidoptera, Psychidae, Oiketicinae, Acanthopsychini). 3 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 27867 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 169 records from EDP Foz-Tua: Fishes – Ecological Monitoring Program [2011-2017]. 2 records from Données naturalistes de Arnoul MATEO. 14 records from Three new species of the primitively segmented spiders from Mt Yuelu, Hunan, China (Mesothelae, Liphistiidae). 4 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 560 records from Data from ILAM surveys conducted by ARCOS in Bugesera landscape for year 2016. 31 records from Inventaire des amphibiens en milieux humides sur le site de Fay-sur-Lignon. 5 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 156 records from Colección de Poales del Museo Botánico CORD - IMBIV. 1603 records from NWTRC JP04 Aerial Surveys 2014-2015. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 165 records from Inventaire et suivi Odonates. 11198 records from Overvåking av åpen grunnlendt kalkmark i Oslofjordområdet. 25 records from Happywhale - Long-finned Pilot Whale in North Atlantic Ocean. 19 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 26 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 6006 records from Herbarium Universitatis Daugavpiliensis. 3 records from Collection Coleoptera SMF. 224 records from Colección de Anelidos del Museo de Historia Natural Marina de Colombia - Makuriwa. 14 records from Five new species of freshwater crabs of the genera Ghatiana Pati & Sharma, 2014 and Sahyadriana Pati & Thackeray, 2018 from India (Decapoda: Brachyura: Gecarcinucidae). 253 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 61 records from Zooplankton studies in the different types of water bodies at the Rzhyshchiv city amalgamated territorial community (CATC). 2208 records from marine sediment metagenome Raw sequence reads. 1 records from Description and bioecology of two new species of the genus Cryncus (Orthoptera Gryllidae, Gryllinae) from Cameroon with a key and distribution map of all African species. 1027 records from Inventario de Flora de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. Municipio de El Carmen de Viboral-Antioquia. 29 records from Three new species and two new records of the genus Cotesia Cameron (Hymenoptera: Braconidae) from Iran. 762 records from Vascular Plants from Praia da Vitória (Terceira, Azores, Portugal). 882 records from Inventario de Fauna Vertebrada de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. 1 records from A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae). 1 records from Redescription of Luetkenia elongata (Copepoda: Siphonostomatoida: Pandaridae), an Ectoparasite of Luvarus imperialis (Actinopterygii: Perciformes: Luvaridae), with a New Record from Japanese Waters. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 311 records from disa_satyriopsis_and_associated_species. 2 records from First report of the spider genus Desis (Araneae, Desidae) from China, with description of a new species. 4 records from A new species Cyrtodactytlus Gray (Squamata: Gekkonidae) from western Thailand and the phylogenetic placement of C. inthanon and C. doisuthep. 3 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 31 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 1 records from Review of the North American fauna of Drymeia Meigen (Diptera, Muscidae) and evaluation of DNA barcodes for species-level identification in the genus. 9197 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 2086 records from Field Museum of Natural History (Botany) Fungi Collection. 26242 records from Inventaire de la flore de Gironde 2018. 3 records from Review of the moray eels (Anguilliformes: Muraenidae) of the Red Sea, with description of a new species. 253 records from SJRP - Herbário de São José do Rio Preto. 5 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 1 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 29027 records from WildNet - Queensland Wildlife Data. 462 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 18 records from A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males. 21080 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 28 records from RECORD Orthoptera Data. 2 records from New taxa of extant and fossil primitive moths in South-East Asia and their biogeographic significance (Lepidoptera, Micropterigidae, Agathiphagidae, Lophocoronidae). 170732 records from National Plant Monitoring Scheme - England, Scotland, Wales. 7 records from The Purdue Entomological Research Collection. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 10000 records from 2020_biodiversity_information_specimen. 3 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 234 records from Données naturalistes de Quentin ROME. 137 records from SEWBReC Springtails and allies (South East Wales). 8 records from Scorpions of the Horn of Africa (Arachnida Scorpiones) Part XXIII Buthus (Buthidae), with description of two new species. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 2044 records from Données du/de la naturaliste Vindras Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 903 records from Inventaire de la flore de la Vienne 2015. 310 records from Caracterización de Flora para el plan de Etnodesarrollo de Bahía Cupica, Chocó. 1 records from Description and taxonomic analysis of a tuberculated turtle leech from the Outer Banks, North Carolina, USA, provisionally identified as Placobdella multilineata Moore, 1953 (Hirudinea: Glossiphoniidae). 13 records from Database on reference specimens for medicinal plants of the Euphorbiaceae family, conserved at the CNARP herbarium. 44 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 3 records from Happywhale - Long-finned Pilot Whale in Arctic Ocean. 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 68 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 53 records from The millipede genus Leucogeorgia Verhoeff, 1930 in the Caucasus, with descriptions of eleven new species, erection of a new monotypic genus and notes on the tribe Leucogeorgiini (Diplopoda: Julida: Julidae). 13 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 7 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 63 records from Données de la naturaliste Laurence Beauchamp. 164 records from Ladybirds of Ireland. 1 records from Rutgers University, Chrysler Herbarium - Lichen Collection. 2 records from DBRC Austropotamobius pallipes records 1960 - 2015. 4215 records from Données naturalistes de Bruno OGER. 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 2 records from New species of Silhouettea (Teleostei: Gobiidae) from Qeshm Island, Iran and the DNA barcoding of the Persian Gulf and Oman Sea gobies. 1 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 232 records from Census of waterbird in Benin Flyway. 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 523 records from Calliphoridae y Mesembrinellidae (Diptera) de la Sierra Nevada de Santa Marta. 27 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 120 records from Herpetofauna de los ríos Mondó y Mondocito, municipio de Tadó, Chocó. 2019. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 1052 records from Happywhale - Humpback Whale in Indian Ocean. 1 records from Systematic notes on some leptomedusa species with a description of Neotima galeai n. spec. (Hydrozoa, Cnidaria). 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 71 records from Some Museums-Meloidae-Biodiversity-Records. 4 records from Description of the lucky Cophyla (Microhylidae, Cophylinae), a new arboreal frog from Marojejy National Park in north-eastern Madagascar. 1 records from Happywhale - Mediterranean Monk Seal in North Atlantic Ocean. 41 records from Happywhale - Short-beaked Common Dolphin in North Pacific Ocean. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 2009 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 4 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 3 records from DDT05_2017_12_18. 112 records from UNCW Norfolk Canyon Aerial Survey - Right side - 2015. 2 records from A new four-pored Amphisbaena (Squamata: Amphisbaenidae) from northeastern Brazil. 359 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 193 records from Land and freshwater molluscs of Northern Spain. 3 records from Taxonomic notes on the genus Sinodrepanus Simonis, 1985, with description of the male of S. falsus (Sharp, 1875) (Coleoptera: Scarabaeidae: Oniticellini). 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 15 records from LNE base de données Mulette perlière déclinaison régionale du PNA. 65 records from University of Nebraska State Museum Birds Collection. 18976 records from University of California Santa Barbara Invertebrate Zoology Collection. 4239 records from Fish occurrence in Kama River basin. 76 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 1 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 2 records from Two new species and new records of the Pselaphodes - complex of genera from China (Coleoptera: Staphylinidae: Pselaphinae). 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 6 records from Review of Palpostilpnus Aubert (Hymenoptera, Ichneumonidae, Phygadeuontinae), with the description of ten new species. 1027 records from Entomology Collection at the Natural History Museum of Utah. 504 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 197 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 230 records from BHCB-Briofitas - Herbário da Universidade Federal de Minas Gerais - Briofitas. 1 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 11655 records from ALCB - Herbário Alexandre Leal Costa. 63 records from Australian National Insect Collection. 13 records from University of California, Davis, Center for Plant Diversity - Herbarium. 2 records from A review of the genus Labeo (Teleostei: Cyprinidae) in Sri Lanka. 60 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 903 records from Mycology herbarium, UiT Tromsø Museum. 5 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 1 records from Vasopora ceramica n. gen., n. sp. - a new abyssal cyclostome bryozoan from polymetallic nodules in the Russian exploration area, Clarion-Clipperton Fracture Zone, eastern Pacific Ocean. 16921 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 6 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 134 records from UCM Vertebrate Observations Collection (Arctos). 5 records from Agrostis barikii (Poaceae: Agrostidinae), a new grass species from Western Himalaya, India. 29 records from MLZ Bird Collection (Arctos). 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 10 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 1 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 1 records from Two new species of freshwater, cave-dwelling crabs of the genus Neostrengeria Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae). 1 records from Pseudoscopas carbonelli n. sp. (Orthoptera: Acrididae: Melanoplinae) from southern Brazil, including chromosome complement. 148 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 3 records from A new small-sized Theloderma (Anura: Rhacophoridae) from Laos. 4120 records from Mammal assemblages recorded by camera traps inside and outside the evacuation zone of the Fukushima Daiichi Nuclear Power Plant accident. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 108 records from Données de la structure Communauté d’Agglomération Grand Paris Sud provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Happywhale - Polar Bear in Arctic Ocean. 5 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 6 records from Happywhale - Leatherback Sea Turtle in North Pacific Ocean. 248 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 201 records from NEON Biorepository Zooplankton Collection (Remaining Bulk Taxonomy Sample). 1 records from Geographic structure of genetic variation in the Parachute Gecko Ptychozoon lionotum Annandale, 1905 across Indochina and Sundaland with descriptions of three new species. 4 records from Two new endemic species of Bistriopelma (Araneae: Theraphosidae) from Peru, including a new remarkable horned tarantula. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 13014 records from Herbarium Senckenbergianum (FR) - Fungi. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 21 records from Mastofauna presentes en la ciénaga de Guineo, Riosucio, Chocó. 411 records from Rhinophoridae Recording Scheme - verified via iRecord. 1819 records from AMAPPS Northeast Aerial Cruise Summer 2016. 2 records from Geometridae de France métropolitaine. 4 records from Vegetable Germplasm Occurrence. 4 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 1 records from New host and distribution records for Buprestidae (Coleoptera) from the state of Morelos, Mexico. 1068 records from MAC herbarium - Instituto do Meio Ambiente do Estado de Alagoas - Herbário Virtual REFLORA. 8472 records from Suivi Temporel des Libellules (STELI). 5 records from Museu Paraense Emílio Goeldi - Myriapoda Collection. 8 records from The Trichoptera of Panama. XII. Contributions to the family Glossosomatidae (Insecta: Trichoptera) in Panama. 3532 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 2389 records from The Fish Sampling at Lata Fish Market in Temotu Province, Solomon Islands. 653 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 3153 records from MICA - Muskrat occurrences collected by RATO in East Flanders, Belgium. 321 records from Vegetación de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 2 records from Kinorhyncha specimens of Ryukyu University Museum (Fujukan). 2 records from Unexpected discovery of six new species of Aphyosemion (Cyprinodontiformes, Aplocheilidae) in the Wonga-Wongué Presidential Reserve in Gabon. 2 records from First record of the Cyrtodactylus brevipalmatus group (Squamata: Gekkonidae) from Vietnam with description of a new species. 137 records from Ibaraki Nature Museum, Vascular Plants collection. 20 records from Ensemble des données Orthoptères. 1035 records from Diversity of Spiders from Azorean Trails. 5 records from Plants Of Nnamdi Azikiwe University Herbarium (NAUH) Awka. 116 records from Museo de Historia Natural Universidad de Caldas - Colección de Vertebrados e Invertebrados - Anfibios. 10354 records from Inventaire de la flore de Charente-Maritime 2018. 7 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 3 records from Three new generic records and descriptions of four new species of jumping spiders (Araneae, Salticidae) from Sri Lanka. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 1923 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 77 records from SNH Invertebrate Site Condition Monitoring 2015: Perchhall Loch SSSI. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 1669 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 134 records from Inventaire sur la retenue collinaire du Brousseau (commune de AIRE-SUR-L'ADOUR). 19054 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 5 records from Sechelleptus arborivagus sp. nov., a new arboreal spirostreptid millipede (Diplopoda, Spirostreptidae) endemic to Mayotte Island (Comoros Archipelago), Indian Ocean. 8662 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 1785 records from 3Soil16S. 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 2 records from Sinopyrophorinae, a new subfamily of Elateridae (Coleoptera, Elateroidea) with the first record of a luminous click beetle in Asia and evidence for multiple origins of bioluminescence in Elateridae. 1 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 10 records from Hydraena (s.str.) dinarica, new species (Coleoptera: Hydraenidae) along with further records of Hydraena spp. from Durmitor National Park, Montenegro and comments on the DNA barcoding problem with the genus. 81 records from Alien plants of Sterlitamak. 1847 records from Tidlig oppdagelse og varsling av fremmede arter 2020. 2 records from Discovery Of A New Mayfly Species (Ephemeroptera, Baetidae) Near Cenderawasih University Campus In Papua, Indonesia. 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 1 records from Données naturalistes de Caitlin DAGG. 9 records from Données naturalistes de THÉVENOT Jessica. 58042 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 250 records from Deep Sea fishes (Chondrichthyes, Osteichthyes) in the Southwestern Colombian Caribbean. 1 records from Re-classification of Lycoriella Frey sensu lato (Diptera, Sciaridae), with description of Trichocoelina gen. n. and twenty new species. 35074 records from Inventaire de la flore de Lot-et-Garonne 2017. 6 records from IBF Monitoring of Plant Galls. 1 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 100 records from Données naturalistes de LE GLOANEC Vincent. 3 records from Two new records of palm species for Gabon: Sclerosperma profizianum Valk. & Sunder. and Eremospatha quiquecostulata Becc.. 1704 records from Rare vascular plant species of Transbaikalia (Republic of Buryatia and Zabaikalsky Kray), Russia. 4 records from Two new species of Psephenops Grouvelle (Coleoptera: Byrrhoidea: Psephenidae) from Panama. 402 records from River Biologists' Database (EPA). 8476 records from CABI Africa Invasive and Alien Species data. 614 records from ERBG AVH data. 230 records from Biometría peces Parque Nacional Natural La Paya. 2 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 75 records from Digitalización y Sistematización de las Colecciones Biológicas Nacionales del Instituto de Biología, UNAM (algas, frutos y semillas, hongos, líquenes, xiloteca). 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13868 records from Données faune Nature 18 - 2017. 2 records from The first record of the genus Desertoniscus Verhoeff, 1930 (Isopoda, Oniscidea, Agnaridae) from Europe, with the description of a new species. 2 records from Description of the female and egg of Phantasca phantasma (Westwood, 1859) (Phasmatodea: Diapheromeridae: Diapheromerinae). 8569 records from Phenology and biological traits of migrating salmon (Salmo salar) sampled by trapping in the survey in the Oir river (France). 29 records from Incriminacion De Vectores De Leishmaniasis En La Costa Caribe. 1 records from Notes on west Palaearctic species of the genus Trigonurus Mulsant, 1847 (Coleoptera: Staphylinidae: Trigonurinae). 833 records from Plant species from the sacred and community forests of Mono departement. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 36 records from Etude écologique de la Cité Scolaire Paul Valéry Paris 12ème. 122 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 3342 records from Fungi and Lichens, Outer Hebrides. 1 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 11 records from Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea Oecophoridae: Pleurotinae). 223 records from Museu de Ciències Naturals de Barcelona: BGJBB. 42 records from Great British Bee Count 2015 - Stage 2 (records verified from photo). 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 3 records from Hydromedusae observed during night dives in the Gulf Stream. 1 records from Distribution des Cétacés et Siréniens dans les eaux de Nouvelle-Calédonie. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 2 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2 records from Brown University Herbarium. 89 records from Colección Ictiológica del Museo de Historial Natural, Universidad de Caldas. 133 records from ZUEC-ORT - Coleção de Orthoptera do Museu de Zoologia da UNICAMP. 2 records from Clubiona jiugong sp. nov., the fifth species of C. zilla-group from China (Araneae: Clubionidae). 21315 records from Mississippi Entomological Museum. 6 records from UWIZM Molluscs. 141 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 89 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 19312 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 34 records from Detection and diversity of nitrite oxidoreductase alpha subunit (nxrA) gene of Nitrospina in the marine sediments. 2 records from The spiny theridiid genus Meotipa Simon, 1895 in India, with description of a strange new species with translucent abdomen and a phylogenetic analysis about the genus placement (Araneae, Theridiidae). 994 records from MCP-Aves - Coleção de Aves. 1 records from New species of gall fly (Diptera: Fergusoninidae) from Eucalyptus camaldulensis (Myrtaceae) in southern Australia and its associated parasitoids and inquilines. 11 records from New species and host plant records for Neotropical Rhagoletis Loew (Diptera: Tephritidae). 8 records from Invasive alien species Impatiens glandulifera Royle in the Republic of Karelia. 1 records from Review of the millipede tribe Polydrepanini, with the description of a new species from Kerala state, southern India (Diplopoda, Polydesmida, Paradoxosomatidae, Alogolykinae). 1 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 3 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 9416 records from Collections of Bioclass, school #179, Moscow. 336 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 1823 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 67 records from Plant specimens of Tama City Cultural Foundation. 42 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 1 records from Xenacoelomorpha collection of National Museum of Nature and Science. 4 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 1745 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 22 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 1 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 226 records from Données multi sources collectées par Hanot Christophe, pour l'atlas des Cerambycidae de métropole (lot 2017). 1904 records from Escarabajos coprófagos de la cuenca alta y media del río Bita, Vichada (Colombia). 125 records from Macroinvertebrate groups found on deep-sea volcanic habitats in the Galapagos Marine Reserve in the Eastern Tropical Pacific Ocean: Porifera. 3 records from UWIZM Anoles. 1 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 113 records from Revision of the morphology, phylogenetic relationships, behaviour and diversity of the Iberian and Italian ant-like Tachydromia Meigen, 1803 (Diptera: Hybotidae). 2 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 24 records from On the origin and diversification of the stygobiotic freshwater snail genus Hauffenia (Caenogastropoda: Hydrobiidae) with special focus on the northern species and the description of two new species. 45 records from Small rodents in mountain birch forest 2002-2016. 69 records from Herbarium of the Institute of the problems of Northern development (TMN). 2 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 682 records from St Andrews BioBlitz 2015. 12 records from Monitoreo del oso andino en el Parque Nacional Natural Cordillera de los Picachos - julio y agosto de 2018. 12554 records from Microbial community in marine sediments. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 642 records from Herbier Louis-Marie (QFA) - Collection de lichens. 61 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 460 records from Murciélagos observados en la expedición al Río Apaporis - Proyecto Colombia BIO. 1 records from Morphology and molecules say: Tanytarsus latens, sp. nov. from Finland (Diptera: Chironomidae). 1 records from A new genus and species of natricine snake from northeast India. 2269 records from Atelier de malacologie continentale, 13-14 septembre (Corrèze et Dordogne). Société Limousine d’Étude des Mollusques (SLEM). 4 records from Revisions of two poorly known species of Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) with description of a new species from China. 2 records from Two new cryptic species of Isometrus (Scorpiones Buthidae) from the northern Western Ghats India. 1 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 2 records from Grasses of the Forest Herbarium Ibadan (FHI) Nigeria. 2 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 1 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 1174 records from Southern Highlands Nature Map. 1 records from Night stalkers from above: A monograph of Toxicodryas tree snakes (Squamata Colubridae) with descriptions of two new cryptic species from Central Africa. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 49 records from Equinodermos de las unidades ecológicas someras Expedición Seaflower Serranilla2017 - Proyecto Colombia BIO. 256 records from Colección Ictiológica del Museo de Historia Natural de la Universidad de la Amazonia (UAM-P). 1 records from The first hygropetric Platynectes and its larva from eastern China (Coleoptera: Dytiscidae). 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 155 records from Manx Wildlife Trust - Records. 1 records from Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae. 24 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 189 records from Tetranychus urticae collection records in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 1 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 1 records from A New Subspecies Of Chrysolina Sanguineocincta (Crotch, 1871) From Turkey (Coleoptera: Chrysomelidae: Chrysomelinae). 31 records from DMNS Egg Collection (Arctos). 1 records from A new species of Anteon from Zimbabwe (Hymenoptera, Dryinidae). 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 3 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 1 records from A new genus and species of Haplobainosomatidae (Diplopoda: Chordeumatida) from the MSS of the Sierra de Guadarrama National Park, central Spain. 11 records from Pez León en Venezuela. 33 records from Pareronia butterfly specimens at Museum Zoologi Bogor, Indonesia. 2 records from Morphology and phylogeny of scalopine moles (Eulipotyphla: Talpidae: Scalopini) from the eastern Himalayas, with descriptions of a new genus and species. 1281 records from Happywhale - Humpback Whale in Arctic Ocean. 99 records from EDP Foz Tua: Black Wheatear (Oenanthe leucura) (Aves) - Ecological Monitoring Program [2012-2017]. 5 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 93 records from UNCW Hatteras Aerial Survey - Right side - 2015. 17 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 11 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 1623 records from Banksia Woodlands Restoration Project Survey. 9174 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 157 records from Murciélagos de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 78 records from Helechos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 11 records from Observations floristiques PNM issues de la base de données flore du Conservatoire botanique national alpin. 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 21156 records from NBIS Records to December 2016. 40 records from Census of invasive alien plant species of Benin (West Africa) by SOS Biodiversity. 11 records from Happywhale - Risso's Dolphin in North Atlantic Ocean. 139 records from Semillas de árboles del bosque seco tropical de Colombia. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 539 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 1 records from The dark side of pumpkin toadlet: a new species of Brachycephalus (Anura: Brachycephalidae) from Serra do Brigadeiro, southeastern Brazil. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 78 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 12093 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 33 records from Wildlife in the City observations between October 2016 - 02 January 2019. 804 records from Données naturalistes de MOREAU Patrice. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 1 records from A New Record From The Genus Callicera Panzer, 1809 (Insecta: Diptera: Syrphidae) From India. 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 4401 records from CNMT - Herbário Centro Norte Mato Grossense. 2 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 1 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 45 records from Coléoptères Silphidés du département du Loiret. 6 records from Données du/de la naturaliste Jarry Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 16095 records from Tanami Pipeline Project Records. 2 records from Phylogenomic re-evaluation of Triaenonychoidea (Opiliones: Laniatores), and systematics of Triaenonychidae, including new families, genera and species. 31150 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 1 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 295 records from Données du/de la naturaliste Anjuerer Jack provenant de la base de donnée du SINP Île-de-France CETTIA. 222 records from Investigación Registros de Libélulas Parque Nacional Natural Tatamá 2017. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 4 records from Taxonomy of the Neolycaena (Rhymnaria) davidi (Oberthür, 1881) species group with the description of two new taxa from Russia and China (Lepidoptera, Lycaenidae). 25 records from The Fungal Collection at the Botanische Staatssammlung München. 851 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 5 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 4772 records from Phanerogamic Botanical Collections (S). 552 records from 1999-2020 Capercaillie Annual Lek Monitoring, Summary Data. 24449 records from Insects, Outer Hebrides. 5 records from Review of the genera Pristocera Klug and Pristepyris Kieffer (Hymenoptera Bethylidae, Pristocerinae) of Russia and adjacent territories. 995 records from Herbarium specimens of Hokkaido University Museum. 234 records from Philippine Mollusk Symbiont - ICBG Collection. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 3 records from Sonerila konkanensis (Melastomataceae), a new species from South Goa, India. 8 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 13 records from Listado de crustáceos zooplanctónicos de laguna Verde-Páramo de Rabanal-Boyacá. 1 records from A new species of Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae; Conocephalinae; Copiphorini) from India. 19 records from Revision of the genus Platyscelis Latreille, 1818 from China (Coleoptera: Tenebrionidae: Platyscelidini). 1 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 550 records from Greendale Creek and Curl Curl Lagoon Bird Survey 2017 to 2019. 31 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 10 records from Meadow katydids (Orthoptera: Tettigoniidae: Conocephalini) from the Central-West Region of Brazil: Morphological, bioacoustic and cytogenetic study. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 244 records from Vascular plants occurrences in Dokdo islands, Korea, based on herbarium collections and legacy botanical literature. 63 records from Happywhale - Bryde's whale in South Atlantic Ocean. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 8 records from A review of Spathipheromyia (Diptera: Muscidae) from Argentina with the description of an extra-large new species. 241 records from Données du naturaliste Danten Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 2 records from A new species of the genus Mawenzhena Alexis & Delpont (Coleoptera Scarabaeidae: Cetoniinae: Goliathini) from South Korea. 117 records from Marine Turtles. 7377 records from Diversidade e ocorrência de peixes do lago Niassa (2006-2018). 14 records from New Mexico Museum of Natural History and Science (NMMNHS) Insect specimens (Arctos). 1854 records from Long-term monitoring of primate, bird, and ungulate populations 2010-2020 for protected area management, Keo Seima Wildlife Sanctuary, Cambodia. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 330 records from The InBIO Barcoding Initiative Database: Lacewings (Neuroptera) 02. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new genus and three new species of nemacheilid loaches from northern Irrawaddy drainage, Myanmar (Teleostei: Cypriniformes). 240 records from Evaluación del macrobentos de la plataforma continental del Caribe colombiano. 2 records from Two new species of the genus Tylostega Meyrick, 1894 (Lepidoptera: Crambidae) from China, with a list of all the known species in the world. 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 10 records from UNCW PAX Aerial Survey - Left side - 2017. 1 records from On the new monotypic wolf spider genus Ovia gen. nov. (Araneae: Lycosidae, Lycosinae). 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 590 records from Thibaut_LACOMBE_2017_12_18. 423 records from Colección de Bacterias del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 1940 records from Données faune ZNIEFF de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 1 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 167 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 1 records from Two new and potentially highly threatened Megophrys Horned frogs (Amphibia: Megophryidae) from Indochina’s highest mountains. 721 records from MijnVISmaat - Exotic fish occurrences in Belgium. 5 records from California Soliperla Ricker, 1952 (Plecoptera: Peltoperlidae), Distribution And Taxonomic Characters. 2 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 1221 records from Solitary bees collected in a large-scale field experiment in power line clearings, southeast Norway. 1 records from Revision and redefinition of the crematogastrine ant genus Tetheamyrma BOLTON, 1991, with the description of a new species and the first description of the dealate queen (Hymenoptera: Formicidae). 3 records from Redescription and new records of a poorly known leucosiid crab, Pseudophilyra punctulata Chen & Ng, 2003, and description of a new species of Pseudophilyra from Japan (Crustacea: Decapoda: Brachyura). 8181 records from DFO Pacific Groundfish Synoptic Trawl Surveys - Strait of Georgia. 5 records from ant-plant_symbioses. 1 records from SNI California Sea Lions 2014 (aggregated per 1-degree cell). 11 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 4 records from Herbarium Senckenbergianum (FR) - Protista. 85 records from Larvas de Chironomidae (Insecta: Diptera) en un gradiente altitudinal de un río de la Sierra Nevada de Santa Marta - Colombia. 1603 records from Ulster Wildlife ShoreNI iNaturalist records. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 1 records from Données de l'Observatoire de la Faune de Bourgogne. 1 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 3 records from Five new species of Stenochrus (Schizomida: Hubbardiidae) from Oaxaca, Mexico. 35 records from Taxonomy and distribution of pimpline parasitoids (Hymenoptera, Ichneumonidae, Pimplinae) in Ukraine. 9181 records from NEON Biorepository Mammal Collection (Hair Samples). 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 1259 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1 records from New species and new record of Thraulodes Ulmer, 1920 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) from Brazil. 396 records from Hawthorne Canal Birdwatching Survey. 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 34 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 35 records from Echinoderms from the Seaflower Biosphere Reserve. 3 records from Description of a new species of the genus Pseudepitettix Zheng (Orthoptera Tetrigoidea: Cladonotinae) from China. 1524 records from EVB herbarium - Herbário Evaldo Buttura - Herbário Virtual REFLORA. 1 records from A new species of Oryttus Spinola, 1836 from the United Arab Emirates and Tunisia with identification key to Palaearctic species (Hymenoptera, Crabronidae). 3 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 106 records from Condrictios del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 4615 records from Allan Herbarium (CHR). 1383 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 22 records from Données opportunistes collectées par les agents du Département des Landes. 1 records from A novel member of the Hemidactylus brookii complex (Squamata: Gekkonidae) from the Western Ghats of Maharashtra, India. 9 records from Artemia (Crustacea, Branchiopoda, Anostraca) cyst bank (IATS-CSIC). 3 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 2 records from Review of the genus Typhloiulus Latzel, 1884 in the Dinaric region, with a description of four new species and the first description of the male of Typhloiulus insularis Strasser, 1938 (Diplopoda: Julida: Julidae). 5 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture à Paris. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 54 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 141 records from Herbario del Museo de Historia Natural C.J. Marinkelle. 2061 records from SSNATV_2017_12_18. 76 records from Données naturalistes de THENARD Jodie. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 5 records from Invasive alien species Noccaea caerulescens (J. Presl & C. Presl) F. K. Mey. in the Republic of Karelia. 55 records from Cambios ultraestructurales de células espermáticas de capitán de la sabana Eremophilus mutisii sometidas a criopreservación. 392 records from Aves de la expedición en la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 38 records from Distribution of Aureoboletus projectellus in Europe. 16 records from Wild boar culled on the National Forest Estate Scotland 2018-19. 396243 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 2814 records from Canadian Museum of Nature Herbarium. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 1131 records from eDNA_Subseafloor. 2 records from Happywhale - South American Sealion in South Atlantic Ocean. 15 records from Chronicle of Nature - Phenology of Mushrooms of Kaniv Nature Reserve. 1127 records from marine sediment metagenome Metagenome. 13 records from Colección de macroalgas de la costa Argentina (IADO-UNS-CONICET). 1007 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 2 records from Invasive Plant Atlas of the MidSouth (IPAMS). 314 records from Tejidos colectados en la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia.. 51 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1 records from Happywhale - Indian Ocean bottlenose dolphin in Indian Ocean. 91 records from Données naturalistes de EL ATTAR SOFI OUMAYMA. 1449 records from Biodiversity of the Desna river valley and its tributaries. 34 records from Dynamics of Submerged Aquatic Vegetation in the Patos Lagoon estuary. 1 records from On the taxonomy of the genera Planovalvata Dubatolov & Kishida, Stigmatophora Staudinger and Pseudomiltochrista Dubatolov & Bucsek, with description of one new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 3 records from The genus Syntozyga Lower (Lepidoptera, Tortricidae) in China, with descriptions of two new species. 2882 records from SYKO Herbarium Moss Collection. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 74 records from New species of Sericini from Sri Lanka (Coleoptera, Scarabaeidae). 20 records from Observations de cétacés en Méditerranée par le Groupe d'étude des Cétacés de Méditerranée de 2012 à 2017. 2269 records from Fitoplancton de la provincia oceánica del mar Caribe colombiano. Diez años de historia. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 10681 records from SEWBReC Bees, Wasps and Ants (South East Wales). 16 records from Biodiversity monitoring in Brunswick Valley Heritage Park Mullumbimby. 2 records from Liogenys Guérin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae Diplotaxini) from the Chacoan Province and its boundaries: taxonomic overview with four new species. 4 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 50 records from Anfibios y reptiles de la expedición Monte y Pinal, Boyacá - Proyecto Boyacá BIO. 2 records from A new species of Potentilla (Potentilleae, Rosaceae) from central China, with reference to molecular and morphological evidence. 3 records from First record of the leafhopper tribe Adelungiini Baker (Hemiptera, Auchenorrhyncha, Cicadellidae: Megophthalminae) from Turkey, with notes on Achrus albicosta (Kusnezov, 1929). 5484 records from New Zealand Arthropod Collection (NZAC). 126 records from Canadian Museum of Nature Bird Collection. 6322 records from Mise en place d'un suivi scientifique des odonates pour la production d’indicateurs de biodiversité. 20 records from Morphological phylogenetic analyses and taxonomic revision of the Panorpa davidi group (Mecoptera: Panorpidae). 5 records from New taxa and notes of katydids from the tribe Meconematini (Orthoptera: Meconematinae) from Brunei Darussalam (Part 2). 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 311595 records from Hakai Institute Juvenile Salmon Program. 2 records from A new species of Girdled Lizard (Squamata: Cordylidae) from the Serra da Neve Inselberg, Namibe Province, southwestern Angola. 15 records from Three new species of Miroculis from the Serra da Mocidade National Park, Roraima State, Brazil, with new records and checklist of the Leptophlebiidae (Ephemeroptera). 1 records from A new arrowtooth eel of genus Meadia (Synaphobranchidae: Ilyophinae) from Vietnam, South China Sea. 63 records from University of Guam Insect Collection. 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 10 records from Seven new species of Australian peacock spiders (Araneae: Salticidae: Euophryini: Maratus Karsch, 1878). 2100 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 12026 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 258354 records from MGYS00005313. 327 records from Fototrampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 1646 records from Freshwater fish records via iRecord. 223 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 846 records from Ensemble des données Odonates. 12397 records from National Dormouse Database (NDD). 3 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 10 records from Invasive species Lupinus polyphyllus in the Republic of Karelia. 72 records from Identity of parasitoid wasps (Hymenoptera, Braconidae and Eulophidae) reared from aquatic leaf-mining flies (Diptera, Ephydridae) on invasive Brazilian waterweed Egeria densa in South Africa. 1 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 87 records from Données naturalistes de TEISSEDRE BERTRAND. 956 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 80 records from Données du/de la naturaliste PARISOT FRANCK provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 12 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 2 records from Identity of bryozoan species described by Jullien & Calvet from the Bay of Biscay historically attributed to Smittia. 1 records from Contribution to the knowledge of the dentipes group of the genus Brachiacantha (Coleoptera: Coccinellidae). 329 records from Invasive Non-Native Species, Outer Hebrides. 3 records from The comparative study of Alkanna and Huynhia (Boraginaceae, Lithospermeae), with description of a new species in Iran. 3 records from Données naturalistes de PATOUX jean pierre. 3 records from The West Palaearctic Dineura species, focussing on Sweden (Hymenoptera, Tenthredinidae). 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 3 records from A new species of Protonemura Kempny, 1898 (Plecoptera: Nemouridae) from the Ishizuchi range, Shikoku, Japan. 2 records from Contribution to the genus Anomala Samouelle, 1819 (Coleoptera: Scarabaeidae Rutelinae) of China and adjacent regions. Part I: descriptions of two new species and remarks on four species. 55 records from Fauna íctica del río Arquía, en las estribaciones del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 144 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 237168 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 90516 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 2 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 1508 records from SEWBReC Amphibians (South East Wales). 20 records from Données malacologiques des membres du Collectif GERMAIN. 193 records from Sciences participatives sur les espèces animales introduites (EEE-FIF). 100 records from The Broward College Insect Collection. 12 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 41 records from NEON Biorepository Zooplankton Collection (DNA Extracts). 642 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 1 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 4 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 7047 records from Fermanagh Flora. 1 records from Guasuctenus gen. nov., a new Neotropical spider genus of Ctenidae (Araneae). 97 records from Isle of Wight non-native invasive species. 1 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 50 records from Amphibians (Amphibia, Anura and Caudata) and reptiles (Reptilia, Squamata) from the headwaters of Río Guázaro on the Caribbean versant of Veraguas province, western Panama. 581 records from Floristic records in the Moscow and Novgorod regions. 472 records from Weber State University Herbarium. 2 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 1 records from An annotated checklist of the Iranian Brentidae (Coleoptera: Curculionoidea). 78 records from Données de la naturaliste Anna Even. 3 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 1 records from An interesting new species of Kamimuria (Plecoptera: Perlidae) from China, with notes on K. grandispinata Du & Sun. 2 records from New record of the steppe longhorn beetle species Phytoecia (Musaria) argus (G. F. Frölich, 1793) (Cerambycidae: Lamiinae) in Bulgaria. 10 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 16 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 6 records from Correctly mating: on the actual female of Hibana talmina Brescovit and the description of H. labonita sp. n. (Araneae, Anyphaenidae). 43 records from KYMA boat-based surveys in Thyrrhenian Sea and Ionian Sea. 63 records from Algas Marinas registradas en Providencia y Santa Catalina durante la Expedición Seaflower 2019 - Proyecto Colombia BIO. 656 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 17 records from Happywhale - Fin Whale in Arctic Ocean. 2758 records from Mayfly (Ephemeroptera) records from Britain and Ireland, via iRecord. 1 records from Transfer of the Namibian Argistes africanus Simon, 1910 (Araneae: Liocranidae) to Afroceto Lyle & Haddad, 2010 (Trachelidae), with a new synonym. 7 records from A new species of the spider genus Wirada (Araneae, Theridiidae) from Mexico, with taxonomic notes on the genus and a key to the species. 3 records from Two new species of the armored spider genus Tetrablemma O. P. - Cambridge, 1873 from northern South America (Araneae: Synspermiata: Tetrablemmidae). 9 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 1 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 37021 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 1252 records from Censos de aves en los municipios de Honda (Tolima) y Guaduas (Cundinamarca) - BIO Alas, cantos y colores. 6 records from Données naturalistes de MICHELOT MARC. 1073 records from SIM-Fungal records compiled by Joan Montón. 9644 records from Western Australian Museum provider for OZCAM. 525 records from Caracterización y monitoreo de fauna silvestre en el área de influencia directa de Hidrocasanare- Yopal del 2014 a 2017. 6 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil. 2 records from Plantas vasculares del Herbario JBN del Jardín Botánico Nacional, Chile. 3 records from First records of Edwardsiana sociabilis (Ossiannilsson, 1936) and Laburrus pellax (Horváth, 1903) (Hemiptera, Auchenorrhyncha: Cicadellidae) in Switzerland. 246 records from NRW Regional Data: South East Wales Non-sensitive species. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 62 records from Données du/de la naturaliste Wroza Stanislas provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Virotia azurea (Proteaceae: Macadamieae), a striking new species endemic to New Caledonia and notes on V. francii and V. leptophylla. 3 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 2 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 279 records from Flora asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 1 records from University of Hawaii Insect Museum. 1 records from Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Happywhale - Striped Dolphin in North Atlantic Ocean. 6 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 10 records from Taxonomic revision of Guapinannus Wygodzinsky, 1951 (Hemiptera: Schizopteridae), with description of 19 new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 4 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 2 records from A new species and new distributional records of Haroldius Boucomont, 1914 (Coleoptera: Scarabaeidae: Scarabaeinae) from southern Africa. 12 records from Yuelushannus gen. nov. (Araneae, Linyphiidae) from China. 10353 records from photoautotrophic_biofilm. 9200 records from NatureShare. 2465 records from Elaboration de table de tarif de cubage multispécifique (I). 6 records from On three new oonopid species from China and the discovery of the male Orchestina bialata Liu, Xiao & Xu, 2016 (Araneae: Oonopidae). 10 records from MVZ Herp Observations (Arctos). 117 records from Cercle des mycologues de Montréal Fungarium (CMMF). 7 records from CRC HRC Shore-based Surveys KB11 2013-2015. 10 records from Invasive alien species Epilobium adenocaulon Hausskn. in the Republic of Karelia. 47 records from Plants Of The Green Line - Woolsthorpe Section. 117 records from Inventaire du site Pierre Fabre de Cahors. 68 records from Données naturalistes d'Olivier LAURENT. 161 records from Données naturalistes de RAYNARD Philippe. 4 records from Mystus prabini, a new species of catfish (Siluriformes: Bagridae) from Arunachal Pradesh, north-eastern, India. 302 records from CSIC-Real Jardín Botánico-Colección de Hongos (MA-Fungi). 1 records from Coleção de Coleoptera da Universidade de Brasília. 175 records from Colección Mastozoológica-Museo de Historia Natural Unillanos. 36 records from Natterjack Toads of Ireland. 7 records from New synonyms, combinations and status in the Chinese species of the family Meloidae Gyllenhal, 1810 (Coleoptera: Tenebrionoidea) with additional faunistic records. 3100 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 3 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 10770 records from Eyre Peninsula's Bird Monitoring Program. 3 records from VIT - Lepidotheca (The Natural History Museum of Álava). 98 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 4 records from Colombia Bahia Malaga (aggregated per 1-degree cell). 381 records from Collection of symbiotic copepods associated with Caribbean invertebrates. 7766 records from NeoWild Brownsberg Nature Park Camera trap Monitoring 2016-2017. 298 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 7394 records from Arizona State University Hasbrouck Insect Collection. 423 records from Invasive Alien Species Occurrence in Ghana. 368 records from Plantas de la expedición en el páramo El Consuelo, Boyacá - Proyecto Boyacá BIO. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 5082 records from Vascular plant herbarium TRH, NTNU University Museum. 191 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 490 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 20 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 19 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 1341 records from Records of the Australian National Botanic Gardens Seedbank. 8 records from Abundant box jellyfish, Chironex sp. (Cnidaria: Cubozoa: Chirodropidae), discovered at depths of over 50 m on western Australian coastal reefs. 3 records from Happywhale - Adelie Penguin in Southern Ocean. 2624 records from MDFRC macroinvertebrate survey. 132 records from Parc_Naturel_Régional_des_Préalpes_d'Azur_2017_12_18. 3 records from Happywhale - Risso's Dolphin in South Pacific Ocean. 4 records from A new species of Synotaxus and the first chromosomal study on Synotaxidae, presenting a rare XY sex chromosome system in spiders (Araneae, Araneoidea). 1 records from A new species of the genus Gracixalus (Amphibia: Anura: Rhacophoridae) from Mount Jinggang, southeastern China. 2 records from Ukamenia Oku, 1981 (Lepidoptera: Tortricidae: Olethreutinae), new record for Thailand with descriptions of a new species. 583 records from MoJ BioBlitz August 2018. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 18 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 2 records from A strikingly coloured new giant millipede from Vietnam has copycat in Borneo (Diplopoda, Spirostreptida, Harpagophoridae). 1 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 6540 records from UF FLMNH Ichthyology. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 46 records from Fauna anfibia asociada al bosque del resguardo indígena Cuti, municipio de Unguía, Chocó. 2020. 12429 records from RECORD Vascular Plant Data. 2 records from A new species of Bolitoglossa (Caudata: Plethodontidae) of the Bolitoglossa franklini group from an isolated cloud forest in northern Guatemala. 137 records from Conchological Society of Great Britain & Ireland: non-marine molluscs (Channel Islands). 581 records from Expedición ornitológica en los municipios de Fusagasugá, Pasca y Silvania, Cundinamarca - BIO Alas, cantos y colores. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 10 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 5 records from Three new species of Ischioscia Verhoeff, 1928 (Isopoda, Oniscidea, Philosciidae) from Serranía de Perijá, Andean Cordillera, Colombian Caribbean. 1 records from Family groups of Diopsoidea and Nerioidea (Diptera: Schizophora) - Definition, history and relationships. 3514 records from NDFF Wall Plants Monitoring Program. 1 records from Checklist and a new species of Lippia (Verbenaceae) from the Diamantina Plateau, Minas Gerais, Brazil. 4 records from K-State Museum of Entomological and Prairie Arthropod Research. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 15 records from Anfibios y reptiles de la expedición en el cañon medio del Chicamocha, Boyacá - Proyecto Boyacá BIO. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 242 records from New data on the dragonfly fauna of the Moulouya River Basin and the Oriental Region, Morocco (Odonata). 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 1 records from Two more new Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from Tamil Nadu, India. 162 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 5994 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Macedomeris, a new monotypic doderiinine genus (Diplopoda, Glomerida) from a cave in North Macedonia, Balkan Peninsula. 9 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 7 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 52462 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 3 records from The genus Stactobiella Martynov (Trichoptera, Hydroptilidae) in Japan. 2 records from Integrative descriptions of two new species of Dugesia from Hainan Island, China (Platyhelminthes, Tricladida, Dugesiidae). 5 records from A northern range extension of a Canadian species of Special Concern, Dielis pilipes (Hymenoptera: Scoliidae), in the Okanagan Valley of British Columbia. 346 records from Birds and plant species near Petushki town (Vladimir region). 16314 records from Données naturalistes de Monsieur François FOURNIER. 9 records from Jeu de données convention FEGVE-SPN (numéro 2). 3 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 2 records from A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from Cu Lao Cham Islands, central Vietnam. 5 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 3 records from A review of the genus Trachystolodes Breuning, 1943 (Coleoptera: Cerambycidae Lamiinae: Lamiini). 102 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 75602 records from Hatikka Observation Database. 638 records from Données naturalistes de Monsieur JOURDE Rémi. 4 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 3850 records from Galiano Island BC Canada Marine Zoology 1893–2021. 22 records from DNA Barcoding and Integrative Taxonomy of the Heterolepisma sclerophylla species complex (Zygentoma: Lepismatidae: Heterolepismatinae) and the Description of Two New Species. 1 records from A survey of East Palaearctic Gnaphosidae (Araneae). 5. On Synaphosus from Central Asia. 57 records from Images and observations of mostly edible plants in Stephen Barstow’s Edible Garden in Norway, taken between 2005 and 2014. 93 records from ProDelphinus Peru Leatherback Tracking Project (aggregated per 1-degree cell). 10 records from Description of three new species of biting midge of the genus Atrichopogon Kieffer (Diptera: Ceratopogonidae) from Brazilian Amazon. 1 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 49 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 6 records from New species and stages description of Traverella Edmunds, 1948 (Ephemeroptera Leptophlebiidae) from Northeast Brazil. 13354 records from NSW AVH data. 6 records from A new species of Anurophorus (Collembola: Isotomidae) from South Korea, with notes on its molecular data. 1 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 2 records from A new species of Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 792 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 56 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 2 records from Happywhale - Southern Bottlenose Whale in Southern Ocean. 4807 records from South Australian Museum Australia provider for OZCAM. 1 records from A new species of Tapiena (Orthoptera: Tettigonioidea: Phaneropterinae) from Brunei Darussalam (Borneo, Southeast Asia). 18339 records from Seasearch Marine Surveys in Ireland. 5 records from Three new ghost moths of the genus Oxycanus Walker, 1856 from Australia (Lepidoptera: Hepialidae). 9 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 67 records from Colección de Polypodiales, Proteales, Psilotales y Ranunculales del Museo Botánico CORD - IMBIV. 5 records from Descriptions of eight new species of the genus Parancistrocerus Bequaert (Hymenoptera: Vespidae: Eumeninae), with a key to the Oriental species. 13 records from Georgian Academy of Sciences, Institute of Botany, National Herbarium of Georgia. 5 records from Five species of the genus Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) from China. 7 records from Three new species of earthworms (Oligochaeta: Megascolecidae) from Yunnan Province, China. 9005 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 4375 records from HBRG Vertebrates (not Badger) Dataset. 7 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 277 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 1348 records from Inventory of Wari maro forest (Benin). 3793 records from Fauna presente en el proyecto Minera de Cobre Quebradona, municipio de Jericó. 43015 records from Fish specimens of Kagoshima University Museum. 74 records from RECORD Odonata Data. 7 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 7 records from UTEP Invertebrates (Arctos). 88368 records from Lithuanian Lepidoptera and Odonata. 7 records from New records and geographic distribution of the sympatric zones of unisexual and bisexual rock lizards of the genus Darevskia in Armenia and adjacent territories. 774 records from Fish occurrence in Kuban River basin. 1 records from Taxonomic revision of the species of Colletes Latreille, 1802 (Hymenoptera: Colletidae: Colletinae) found in Chile. 1 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 243039 records from Observations naturalistes des Amis de BioObs.. 693 records from Happywhale - Leopard seal in Southern Ocean. 46 records from Geneva Herbarium – General Collection (G). 3 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 1011 records from Vegetación de los remanentes de bosque andino, municipio de San Francisco (Cundinamarca). 14 records from Dimitri Multeau Loir-et-Cher Nature. 113 records from Registro de una poblacion de Abejorros en los departamentos de Boyacá y Cundinamarca. 10 records from Données opportunistes sur les odonates. 2360 records from SPSF - Herbário Dom Bento José Pickel. 24 records from Census of animals species through Benin from 2011 to 2019. 127 records from Some thecate hydroids (Cnidaria: Hydrozoa) from off New Caledonia collected during KANACONO and KANADEEP expeditions of the French Tropical Deep-Sea Benthos Program. 1 records from Taito adrik, a new harvestman species from the Área de Conservación Privada Panguana, Peruvian Amazonia (Opiliones: Laniatores: Cosmetidae). 1812 records from Données Entomologiques A. HORELLOU 1988-2018. 12 records from 2017 Onwards Rare Invertebrates in the Cairngorms Shining Guest Ant Survey Data. 5 records from Adding stars to the Chromodoris (Nudibranchia, Chromodorididae) galaxy with the description of four new species. 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 245 records from Ecology, phenology and wintering behavior of Anatidae in the wetlands of Souk-Ahras (north-eastern Algeria). 185 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from New species and records of Chasmogenus Sharp, 1882 from the southwestern margin of the Guiana Shield (Coleoptera: Hydrophilidae: Acidocerinae). 632 records from 2019_NSMK_PL. 1193 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1135 records from Terrestrial avian occurrences in the context of urbanization of Central Chile. 1 records from Herbier National de Guinée (HNG). 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 4 records from Taxonomy of Central American water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 255 records from Iowa State University Fishes Collection. 595 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 325 records from Inventaire malacologique de la RNR des Marais de Stors. 60995 records from Natural History Museum (London) Collection Specimens. 6 records from Notes on the genus Perittopus Fieber, 1860 (Hemiptera: Heteroptera: Veliidae with descriptions of three new species from Indochina. 34 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 442 records from WOLL AVH data. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 1 records from A new genus and new species assigned to Macrophthalmidae (Decapoda: Brachyura: Thoracotremata) from the Ryukyu Islands, Japan. 56 records from TULGU Herbarium: Tula Oblast collections of vascular plants. 42 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 8761 records from Colección de Peces de Agua Dulce del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 546 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Données de présence collectées sur les écrevisses. 2053 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 3 records from Three new species of the subterranean genus Guiodytes from Guangxi, China (Coleoptera: Carabidae: Clivinini). 1 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 4 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 211 records from Données des collections d'algues du MNHN. 1 records from Redescription of Alopecosa albostriata (Araneae: Lycosidae) based on specimens from Siberia. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 2 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 1 records from Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile. 576 records from Zooplancton del estrecho de Bransfield y alrededores de Isla Elefante, verano austral 2019-2020, durante la VI Expedición Científica de Colombia en la Antártica. 2 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 6 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 23 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 2 records from Grand Voyeux - Suivis scientifiques. 1 records from Pyrrosia sarthalensis, a new species of Polypodiaceae from Kathua District, Jammu and Kashmir, Western Himalaya, India. 15 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 190 records from Données naturalistes 2019 de Bruno DAUGET. 6 records from Les spermaphytes de l'Herbier du Centre National de Floristique de Côte d'Ivoire: quatrième partie.. 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 290 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 4 records from Troglocaris (Xiphocaridinella) kumistavi sp. nov., a new species of stygobiotic atyid shrimp (Crustacea: Decapoda: Atyidae) from Kumistavi Cave, Imereti, Western Georgia, Caucasus. 102 records from Ocurrencias de visón (Neovison vison) en el Sistema Nacional de Áreas Silvestres Protegidas del Estado de Chile (SNASPE-CONAF). 1 records from A new species and new record of Polycystididae (Rhabdocoela: Kalyptorhynchia) from China. 1162 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 17 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 137 records from Glasgow Museums BRC: Chrysomelidae. 274 records from 2019-KNAM-PL. 3 records from Carnivorous sponges (Porifera, Cladorhizidae) from the deep South Pacific (New Caledonia) with the description of three new species of the genus Abyssocladia and remarks on genus Cercicladia. 4 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Registro de Mono Choyo (Lagothrix lagotricha lugens) en Chámeza-Casanare. 11 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 60 records from Taxonomy and host-plant relationships of the psyllid genus Mitrapsylla (Hemiptera: Psylloidea: Psyllidae) in Brazil. 14 records from Tití Gris (Saguinus leucopus) en remanentes de bosque de los departamentos de Caldas y Antioquia. 3 records from Kenai National Wildlife Refuge, Alaska (KNWR) Mammal observations (Arctos). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 3 records from A new species of the genus Colilodion Besuchet, 1991 (Coleoptera: Staphylinidae: Pselaphinae) from Mindanao, the Philippines. 2 records from Happywhale - Dusky Dolphin in South Pacific Ocean. 1 records from Données naturalistes de CARON Nicolas. 14 records from Unexpected diversity of the genus Collarina Jullien, 1886 (Bryozoa, Cheilostomatida) in the NE Atlantic-Mediterranean region: new species and reappraisal of C. balzaci (Audouin, 1826) and C. fayalensis Harmelin, 1978. 74 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 2 records from The spider family Oecobiidae (Arachnida: Araneae) in Iran, Afghanistan and Turkmenistan. 97 records from Underwater fish visual census in the Azores from 1997 to 2015. 12 records from The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae. 1 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 2 records from A new species of Glyptothorax (Teleostei: Sisoridae) from the Brahmaputra River basin, Arunachal Pradesh, India. 7 records from Données naturalistes de Bernard Lalanne-Cassou. 3 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 40 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 895 records from Avifauna asociada a paisajes rurales degradados en la vereda San Luis, Barrancabermeja - Santander. 27 records from Synopsis of Schizanthus: list of specimens examined. 2 records from Morphological description and DNA barcoding of Hydrobaenus laticaudus Saether 1976 (Diptera: Chironomidae: Orthocladiinae) from Amur River basin (Russian Far East). 8 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 739 records from Biodiversidad asociada a la declaración del Área Protegida en el Pueblo Indígena EPERARA SIAPIDARA, Resguardo Calle Santa Rosa, Timbiquí (Cauca). 6 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 1 records from A new species of frog in the Litoria ewingii species group (Anura: Pelodryadidae) from south-eastern Australia. 310177 records from SEWBReC Birds (South East Wales). 807 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2016. 5726 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 4264 records from Weed plants of the European part of Russia. 6 records from Occurrence data of Eremohaplomydas, Haplomydas, and Lachnocorynus (Diptera: Asiloidea: Mydidae). 23 records from Middlebury College Insect Collection Coccinellidae. 31 records from Robert Forsyth Terrestrial Gastropods Collection. 1587 records from Prospecting of extreme microbial ecosystems associated to minerals (microbialites, microbial mats and endoevaporites) in Puna, Wetlands and Salars of Argentina, Chile and Bolivia. 240 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 1 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from A new species of the ghost shrimp genus Neocallichirus Sakai, 1988 from Iran, and new record of N. manningi Kazmi & Kazmi, 1992 (Decapoda: Axiidea: Callianassidae). 14043 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 2 records from Description of the second species of Synhalcurias Carlgren, 1914, Synhalcurias kahakui sp. nov. (Actiniaria: Actinernidae) with redescription of S. elegans (Wassilieff, 1908). 19780 records from Eulachon migration bottom trawl surveys. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6347 records from MARINe/PISCO: Intertidal: MARINe Long-Term Monitoring Surveys: Sea Stars and Katharina. 9741 records from marine sediment metagenome Raw sequence reads. 9634639 records from Pl@ntNet automatically identified occurrences. 1 records from A new species of Parafimbrios from northern Vietnam (Squamata: Xenodermatidae). 2183 records from Noctuoidea de France métropolitaine. 340 records from Dolichopodidae of Portugal - dataset 2009-2018. 12 records from Données du/de la naturaliste Provost Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 138 records from Plantas en ecosistemas agropecuarios de la quebrada Piedra Candela, en la altillanura plana del Meta. 1123 records from Données naturalistes d'Alain BERLY. 178 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 20 records from Mantidflies (Neuroptera, Mantispidae) from Tocantins state (Brazil): distribution and identification key. 1475 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 43 records from Données opportunistes. 639 records from Inventaire de l'îlot du Lédénez Vraz. 18584 records from Phenology and biological traits of migrating salmon (Salmo salar) sampled by trapping in the Scorff river (France).. 7173 records from Bird survey with mapping at the permanent sample plots in the Prioksko-Terrasnyi Biosphere Reserve. 2597 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 1 records from The genus Ctenomelynthus (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with the description of three new species and key to the known species. 77 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 3551 records from Données de la flore d’Alsace (SBA). 92 records from Colectas del género Ischnura en el marco del proyecto Divergencia genética y preferencia de apareamiento en Ischnura capreolus e Ischnura cyane en Colombia. 13 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 1 records from DREAL Auvergne - Insectes - 2015. 4633 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 42 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 190 records from NEON Biorepository Benthic Macroinvertebrate Collection (DNA Extracts). 2 records from Contribution to the knowledge of Dialeurodes (Gigaleurodes) Quaintance & Baker (Hemiptera: Aleyrodidae), with description of a new species from China. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from Taxonomic revision of Plyomydas Wilcox & Papavero, 1971 with the description of two new species and its transfer to Mydinae (Insecta: Diptera: Mydidae). 1 records from A new Antillobisium species (Arachnida: Pseudoscorpiones: Bochicidae) from Cuba, with biogeographical and ecological remarks on the genus. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 1925 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 619 records from NHMD Ornithology Collection. 1 records from A new species of the genus Hebius (Squamata: Colubridae: Natricinae) from Hunan Province, China. 80 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 237 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 1 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 395 records from Suivi Odonates. 4285 records from EAC - Herbário Prisco Bezerra. 42 records from Euroants. 3 records from Systematics of Helioandesia tarregai gen. et sp. nov. (Lepidoptera: Yponomeutoidea: Heliodinidae) from the Andes of Northern Chile. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 11 records from Leif Richardson Vermont Bee Specimens. 1526 records from The Nanoeukaryotic plankton Raw sequence reads. 7 records from PRA Sonneur à ventre jaune - étude de répartition. 3629 records from Irish Whale and Dolphin Group. 764 records from Collection Crustacea - ZMB. 2 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 2 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 48 records from SNH Invertebrate Site Condition Monitoring 2015: Tweedwood - Gateheugh SSSI. 60 records from Individuos de Gunnera schultesii L.E.Mora y su respuesta al efecto de la sombra y el tipo de fertilizante sobre su crecimiento en condiciones ex situ. 870 records from Marie-Victorin Herbarium (MT) - Bryophytes. 1 records from iHerbarium. 2390 records from 2019_biodiversity_cooperation_investigation. 386063 records from Compost microbe establishment and growth in agricultural soils. 4406 records from National Benthic Inventory. 2 records from A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae). 29 records from Données de la naturaliste Clémentine Gand. 5 records from New records of two butterflies of the genus Polyommatus Latreille, 1804 (subgenus Agrodiaetus Hübner, 1822) (Lepidoptera: Lycaenidae) from Iraq. 1 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 3704 records from BCE butterfly data expert holiday data throughout Europe. 17 records from The Marine Fauna of New Zealand. Squat lobsters (Crustacea, Decapoda, Chirostyloidea). 172 records from SEFSC GoMMAPPS Vessel Survey 2018 Summer. 144 records from Inventaire biodiversité du site Pierre Fabre de Saint-Sulpice. 1 records from Review of the species of Stenothemus from Southeast China (Coleoptera, Cantharidae). 125 records from Учет боровой птицы на токах. 3239 records from Arthropods from Praia da Vitória (Terceira, Azores, Portugal). 5025 records from Balsfjord Nature Reserves. 10 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 1 records from K herbarium - Royal Botanic Gardens, Kew - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 7 records from A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea). 3748 records from Manx Biological Recording Partnership UNVERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 796 records from Ornithological observations in the Kharkiv region of Ukraine. 2838 records from CAS Entomology (ENT). 930 records from Occurrences of Oxytropis species on the territory of Asian Russia. 50 records from John Clayton's Fijian Moth Collection. 2165 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 158 records from Parásito nemertino Carcinonemertes conanobrieni en langostas espinosas Panulirus argus del departamento de Magdalena. 1 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 12 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 150632 records from Seasearch Marine Surveys in England. 30472 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from HSS-carpoteca (HSS-C) Finca La Orden-Valdesequera (CICYTEX). Junta de Extremadura. 118 records from Données du/de la naturaliste PRATTE Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 23 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 9 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 4 records from Happywhale - Arnoux's Beaked Whale in Southern Ocean. 358 records from SEWBReC Slime Molds (South East Wales). 1530 records from Lichenized fungi of Vietnam (PHH Herbarium, Cryptogam collection). 2 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 1 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 3 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 54 records from Georgia Aquarium/DomSeTCO Leatherback's of Dominica (aggregated per 1-degree cell). 311 records from RHS Fuchsia Gall Mite (Aculops fuchsiae) monitoring. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 5 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 214333 records from Programa de fotomonitoreo de objetos de conservación y amenazas en el Sistema Nacional de Áreas Silvestres Protegidas del Estado (SNASPE). 1 records from A new genus and species of Ingolfiellidae (Crustacea, Ingolfiellida) from the hyporheic zone in the Sierra de la Ventana, and its biogeographic relevance. 637 records from Observations naturalistes de Philippe RAVAT. Inventaire entomologique du Morne Bigot. 9 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 140743 records from Raw sequence reads from soil relic DNA study. 34 records from MVZ Egg and Nest Collection (Arctos). 264 records from Overvåking Røsskleiva NR. 7 records from A new genus and species of cricket from eastern Cuba: the first Antillean true Eneopterinae (Orthoptera: Gryllidae: Eneopterinae). 21417 records from VIS - Non-native fish in Flanders, Belgium. 3 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 1296 records from Herbario Enrique Forero de la Universidad de la Amazonia (HUAZ). 250 records from Coleção de Mamíferos da Universidade Estadual do Norte Fluminense. 45 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 9827 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 150 records from Caracterización florística del cerro Iró, municipio del río Iró, Chocó. 2020. 68 records from LA - University of California, Los Angeles Herbarium. 1750 records from Colección del Herbario de la Universidad de los Llanos. 27 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 1 records from Contribution to the Ichneumoninae (Hymenoptera, Ichneumonidae) of Nepal. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 9 records from Valentin Moser Bats. 11 records from Leafhopper subfamily Ledrinae of the Indian subcontinent: 1. Description of Yelahanka gen. nov. (Hemiptera: Cicadellidae) with seven new species and new combinations. 2625 records from Subtidal macrobenthos monitoring in function of a foreshore suppletion at the Belgian coast, period 2013-2016. 1 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 15 records from Colección de microorganismos asociados a plantas de Cacao. 1 records from Further information on Lolibaia Gorbunov & Gurko, 2017 (Lepidoptera: Sesiidae: Synanthedonini) with description of three new species from tropical Africa. 115 records from Duke University Herbarium Algae Collection. 14413 records from Museums Victoria provider for OZCAM. 1 records from A new species of the genus Parahormius Nixon (Hymenoptera: Braconidae: Hormiinae) parasitic on host pupae of Lyonetiidae (Lepidoptera) from India. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 21 records from Murciélagos de la isla de Providencia. Expedición Seaflower 2019 proyecto Colombia BIO. 806 records from Regroupement de données Rhopalocères. 9 records from Données naturalistes de HENDOUX Frédéric. 12 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 2072 records from LPO_PACA_2017_12_18. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 280 records from Sphaeriid clams. 76 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 62569 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 9 records from New species and findings of Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from Central Asia, with DNA barcoding of known species of the genus. 7 records from Four new cyclophoroid species from Thailand and Laos (Gastropoda: Caenogastropoda: Alycaeidae, Diplommatinidae, Pupinidae). 3 records from Gammaropsis elvirae sp. nov., a widely distributed amphipod (Amphipoda: Photidae) in the Yucatan Shelf, with ecological comments and a key for the genus in tropical America. 8 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Olekminsky. 24 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 5 records from UWIZM Mammals. 1 records from Universidad del Valle de Guatemala - Colecciones Biológicas - Equinodermos. 6977 records from 2019_NSMK_PL_2. 92 records from Sonidos de la Ecoreserva La Tribuna (Neiva, Huila) - Proyecto FIBRAS. 47091 records from INPN - Données flore des CBN agrégées par la FCBN. 170 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Nematodos Chetumal). 4 records from Discovery of leaf-mining Tischeriidae (Lepidoptera) in Colombia and their distribution in the Neotropics. 1 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 21 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) IX. The maculosa species-group, with descriptions of eighteen new species. 1 records from Cladistic analysis and description of a new species of the Brazilian genus Atlantodesmus Hoffman, 2000 (Diplopoda: Polydesmida: Chelodesmidae). 37295 records from Observatoire Pelagis boat surveys 2003-2019. 39382 records from ADDOMEx Tier 3 Experiments: Mesocosm Si with Gulf of Mexico coastal waters. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 14365 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 2691 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 44 records from Collection Pisces SMF. 7 records from Data from: Distribution Pattern of Bivalve in Littoral Zone Gisi Village, Bintan District,Riau Island Province. 225 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2016. 30 records from Three new species of Mesovelia Mulsant & Rey (Hemiptera: Heteroptera: Mesoveliidae) from India. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 6 records from Freshwater Pest Plants. 801 records from Données Odonates du Parc Naturel Régional du Perche. 1 records from Thalictrum nanhuaense (Ranunculaceae), a new species from central Yunnan, China. 2 records from A taxonomic synopsis of Chrysomydas Wilcox, Papavero & Pimentel (Diptera: Mydidae: Mydinae), with first bionomic records for the genus and description of a new species from Brazil. 1 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 2091 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Oir river (France). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 1 records from First record of Africactenus Hyatt, 1954 and redescriptions of two poorly known species of Ctenus Walckenaer, 1805 (Araneae, Ctenidae, Cteninae) from India. 462 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new species of the porcelain crab genus Petrolisthes from the Pacific coast of Panama, with taxonomic notes on closely related species (Decapoda: Anomura Porcellanidae). 515 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 2 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 489 records from Données naturalistes de ROMET Nicolas. 1 records from First Record of Holothuria (Cystipus) dura (Echinodermata: Holothuroidea) from Japan, with Notes on Locomotion. 1 records from SJRP herbarium - Universidade Estadual Paulista Júlio de Mesquita Filho - Herbário Virtual REFLORA. 813 records from TWIC Hedgehog Public Survey. 24 records from UNCW PAX Aerial Survey - Right side - 2016. 214 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 1 records from One new Pseudopoda species group (Araneae: Sparassidae) from Yunnan Province, China, with description of three new species. 291 records from Native Bee Baseline and Effects Monitoring on the Green Mountain National Forest 2015. 141581 records from Estonian Nature Observations Database. 23505 records from Herbarium Willing at Herbarium Berolinense, Berlin (B). 12938 records from 16S rDNA sequencing. 3 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 5100 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé à partir de 2016. 3 records from Review of the genus Trichactia Stein (Diptera: Tachinidae) in the Palaearctic Region, with the description of a new species from Iran and the East Mediterranean. 38 records from NCSM Mammalogy Collection. 3 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 7334 records from HCF herbarium - Universidade Tecnológica Federal do Paraná - Campus Campo Mourão - Herbário Virtual REFLORA. 2 records from Notes on Malagasy Discheramocephalus Johnson (Coleoptera: Ptiliidae). 122 records from Inventaire de la Flore patrimoniale dans la RNN Etang de Saint-Paul avant le 31/12/2017. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 15477 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 47816 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 2 records from Two new cavernicolous Pselaphinae (Coleoptera: Staphylinidae) from southern China. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 802 records from Insect specimens of Toyota City Nature Sanctuary. 4 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 1 records from Nine new species of Enithares (Heteroptera: Notonectidae) from New Guinea, with distributional notes on other species and an updated world checklist. 7 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 1 records from Reproductive Biology of Marine Turtles under Extreme Climatic Conditions (aggregated per 1-degree cell). 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 94422 records from Bryophyte data for Great Britain and Ireland from the British Bryological Society held by BRC: data compiled post-Atlas. 31 records from Registros de mamíferos de los Parques Ecológicos Distritales de Montaña de Bogotá, D.C.. 4735 records from Fife Nature Records Centre combined dataset. 50 records from CHAS Botany Collection (Arctos). 5 records from Four new species of the genus Rhodesiella from Xizang Autonomous Region, China (Diptera: Chloropidae). 32868 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 14 records from Herbarium of Numto Nature Park. 27811 records from Tasmanian Museum and Art Gallery provider for OZCAM. 2 records from Happywhale - Short-finned Pilot Whale in South Atlantic Ocean. 46194 records from Swiss National Mollusca Databank. 3125 records from WIKTROP - Weed Identification and Knowledge in the Tropical and Mediterranean areas. 2 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Fósseis (ZUFMS-FOS). 519210 records from RU-BIRDS.RU, Birds observations database from Russia and neighboring regions. Zoological Museum of M.V. Lomonosov Moscow State University.. 1691 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 1 records from A large hornet mimic clearwing moth of the genus Lamellisphecia Kallies & Arita 2004 (Lepidoptera, Sesiidae) from Nanling, Guangdong, southern China. 1320 records from Eventos de monitoreo de la especie plaga Didymosphenia geminata en cuerpos de agua de la zona centro sur austral de Chile, Etapa I (2016 - 2017). 44 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 5246 records from Meetnetten.be - Egg counts for butterflies in Flanders, Belgium. 55 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Cragbank and Wolfehopelee SSSI. 1 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 28 records from Satellite tracking of rehabilitated juvenile loggerhead, green, and Kemp's ridley turtles in the northeastern USA. 19 records from Mexican species of the genus Orthocentrus (Hymenoptera, Ichneumonidae: Orthocentrinae). 3 records from Review of Poecilimon species with inflated pronotum: description of four new taxa within an acoustically diverse group. 13006 records from Chrysomelidae beetle data from iRecord. 3704 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 4 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 4 records from Happywhale - King Penguin in South Atlantic Ocean. 31190 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 39 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 125 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 510 records from Registros Primates Neotropicales Convocatoria APC. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 63 records from Données naturalistes de William BATIFOIX. 66 records from Spectacled bear database for Peru. 3886 records from Records of Invasive Non Native Species held on the Cofnod database. 3 records from Two new species of Paratanytarsus Thienemann & Bause (Diptera: Chironomidae) from Oriental China. 5 records from New endemic species of freshwater crayfish Parastacus Huxley, 1879 (Crustacea: Decapoda: Parastacidae) from the Atlantic forest in southern Brazil. 5015 records from MHA Herbarium: Collections of mosses from Yana-Indigirka Region, Yakutia, Russia. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 31 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 1 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 1589 records from Flora of Seymskiy Regional Landscape Park. 901 records from White sea picoplankton Metagenome. 13002 records from Données du/de la naturaliste Grosso Eric provenant de la base de donnée du SINP Île-de-France CETTIA. 392 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 1349 records from Happywhale - Gray Whale in North Pacific Ocean. 32418 records from Suivi Temporel des Rhopalocères de France (STERF). 41 records from MalaCo, Journal de Malacologie continentale [2005-]. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 1 records from The Stenus cirrus group (Coleoptera, Staphylinidae) in Fujian, East China. 1 records from Confirmation of Gonioctena rufa (Kraatz, 1879) (Coleoptera: Chrysomelidae) in northeastern Asia, previously misinterpreted as a subspecies of G. viminalis (Linnaeus, 1758), and a new synonym in the genus. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 13 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 21 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 954 records from Mammals Specimens. 26 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 527 records from SIM-XII Jornadas Micológicas El Ilustre Minero. 4 records from Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from Guizhou and Guangxi, China. 124 records from Birds of Grand Kru Liberia. 1 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 1404 records from Lauri Mällo private collection of Lepidoptera. 98 records from Peces del Distrito Nacional de Manejo Integrado Cabo Manglares Bajo Mira y Frontera, Pacífico colombiano - Proyecto Colombia BIO. 3 records from Review of the Swedish Enicospilus (Hymenoptera; Ichneumonidae; Ophioninae) with description of three new species and an illustrated key to species. 203 records from Données de VINCENT Alexis (SAPROX). 1222 records from Plantas de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 5 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 1318 records from Colección Viva del Jardín Botánico de Bogotá. 1882 records from Heleomyzid Recording Scheme - data verified via iRecord. 5 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 12 records from Mammal specimens of Kawasaki Municipal Science Museum. 2 records from Levinsenia species (Annelida: Polychaeta: Paraonidae) from the Sea of Marmara with descriptions of two new species. 6 records from A new species of Laurenceomyia Wagner & Stuckenberg, with a key to species and new records for Psychodidae (Diptera) from Uruguay. 1390 records from Observations de tortues marines en surface sur la côte ouest de La Réunion - Export avril 2018. 1 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 1 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 140 records from Taxa occurrences and composition of benthic macroinvertebrates in Lake Edward system, Uganda. 3 records from Happywhale - Polar Bear in North Pacific Ocean. 146929 records from The CPR Survey. 1 records from Review of the genus Suwallia (Plecoptera: Chloroperlidae) from China with description of Suwallia jihuae sp. nov. from Sichuan Province. 19169 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2015. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 930 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 1 records from Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae). 39765 records from Wikiplantbase #Toscana. 2 records from A new species of Dinotoperla Tillyard, 1921 from the Shoalhaven Catchment, New South Wales, Australia (Plecoptera: Gripopterygidae). 518 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2017. 3 records from New species of Soa Enderlein, 1904 (Psocodea: ‘ Psocoptera’: Lepidopsocidae) from the Western Ghats of India. 18 records from ALTERECO_2017_12_18. 20 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 63 records from Mammal collection NTNU University Museum. 4592 records from Sediment metagenome. 207024 records from BioFokus. 109 records from Registros de la anfibiofauna asociada a la ciénaga de montaño, Carmen del Darién, 2020. 2856 records from Anymals+plants - Citizen Science Data. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 5236 records from Happywhale - Humpback Whale in North Atlantic Ocean. 20 records from Happywhale - Blue Whale in Southern Ocean. 107997 records from ABV - Common breeding birds in Flanders, Belgium (post 2016). 20 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1576 records from Data on the biodiversity of macrophyte communities and associated aquatic organisms in lakes of the Vologda Region (North-Western Russia): macrophytes. 1 records from A new species of Hemidactylus (Squamata: Gekkota: Gekkonidae) from Qara Dagh Mountains, Kurdistan Region, with a key to the genus in Iraq. 1510 records from Oil Beetle Recording Scheme - records verified via iRecord. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 4148 records from EDP Foz-Tua: Phytobenthos – Ecological Monitoring Program [2011-2015]. 2 records from Rehabilitated loggerhead from southern Italy - 2 (aggregated per 1-degree cell). 2 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 1 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 2 records from Yunnanosticta gen. nov., from Yunnan, a new genus from the Sinostictinae, with the description of two new species (Odonata: Zygoptera: Platystictidae). 1 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 1030 records from KUZ Herbarium: collections of vascular plants. 576 records from Herbier National du Gabon. 109 records from Rosa gallica L. in "Medobory" Nature Reserve. 169 records from Biodiversidad de los Ecosistemas Mesofóticos de la Isla de San Andrés. 29558 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 1 records from New data and species of Thecomyia Perty, 1833 (Diptera: Sciomyzidae) from Mitaraka (French Guiana), with notes on the genus. 9 records from New species and records of Perlidae (Plecoptera) from Espírito Santo State, Brazil. 12 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 5656 records from Atlas of the dragonflies and damselflies of West and Central Asia. 459 records from Société_Française_d'Odonatologie_2017_12_18. 1 records from Congruence between morphology and molecular data supports the distinction between the snapping shrimps Alpheus macrocheles and A. amblyonyx (Caridea, Alpheidae). 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 3 records from Gibbosaverruca weijiai, a new verrucid (Crustacea, Thoracica) species from the Weijia Guyot deep-sea seamount in the West Pacific. 60 records from Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 6144 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 1 records from The InBIO Barcoding Initiative Database: Taxonomic notes on Portuguese Microlepidoptera II. Cochylimorpha punctiferana (Ragonot, 1881). 2 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 55 records from Black grouse annual lek surveys by study groups in Speyside, Donside, Angus Glens and the Southern Uplands for the period 2018 to 2021. 2279 records from Données du Parc Naturel Régional de la Haute Vallée de Chevreuse provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 1066 records from Biodiversity mapping in connection with Nature in Norway (NIN) in Vestland, Troms and Finnmark, Norway (2019). 511 records from Plantas del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 1 records from First Record Of Pseudepipona Kazenasi Kurzenko, 1974 (Hymenoptera: Vespidae) From Mongolia. 2 records from Three new species of genus Pylaemenes Stål (Phasmatodea: Heteropterygidae: Dataminae) from Vietnam. 25 records from Re-description of Strandesia sanoamuangae Savatenalinton & Martens, 2010 and description of a new species of Strandesia (Crustacea, Ostracoda) from Grande Terre, New Caledonia. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 4 records from On the taxonomic status of Holothuria (Holothuria) tubulosa (s. s.) from the Algerian coast with the description of a new Mediterranean species, Holothuria (Holothuria) algeriensis n. sp. (Echinodermata: Holothuroidea: Holothuriidae). 13 records from Suivi de la reproduction des Lamproies de Planer sur les sites Natura 2000 en Seine-et-Marne. 713 records from Albury Wodonga Nature Map. 13 records from Happywhale - Bowhead in Arctic Ocean. 53 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 2 records from Description of new species of Ambrosiodmus Hopkins and Dryocoetoides Hopkins (Curculionidae: Scolytinae: Xyleborini) from Mexico. 4 records from Nine new Agrilus (Coleoptera: Buprestidae, Agrilini) from Palaearctic and Oriental regions. 103 records from Happywhale - Minke Whale in North Pacific Ocean. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 2 records from CONN. 143 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 15370 records from NHMO Bird collection. 211 records from Post Graduate College Bannu Herbarium. 3967 records from Kherson State University herbarium (KHER), Department of Botany. 36 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 449 records from Plantas de la expedición al municipio de Cimitarra, Santander - Proyecto Santander BIO. 3 records from Impatiens wutaishanensis (Balsaminaceae), a new species from Southeast Yunnan, China. 4 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 81411 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 6818 records from Données de mortalité de la faune par collision avec les véhicules sur le réseau routier de la DIR Centre-Est. 1 records from The Yponomeutidae of the Afrotropical region (Lepidoptera: Yponomeutoidea). 34 records from Sideritis syriaca subsp. nusairiensis and Thymus sipyleus in Mount Lebanon. 45 records from On the genus Berosus Leach (Coleoptera: Hydrophilidae) in the State of Roraima Brazil: description of three new species and new records. 2 records from Hawksbill turtle - Milman Island (aggregated per 1-degree cell). 534 records from Département_du_Var_2017_12_18. 282 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica San cristóbal). 10 records from Five new species of Otacilia Thorell, 1897 (Araneae: Phrurolithidae) from the Wuling Mountain Range, China. 15 records from Holothurians of the genus Peniagone (Elasipodida: Elpidiidae) from the northwest Pacific ocean. 8 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 1693 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 3 records from Two new species of Sabellariidae (Annelida, Polychaeta) from the abyss of eastern Australia. 3 records from Notes on a small collection of phaneropterine bush-crickets (Insecta: Orthoptera: Tettigonioidea) from Central and Southern Madagascar with the description of two new species. 88 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 324 records from Composición y estructura de anfibios en el Parque Nacional Natural Selva de Florencia. 1 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 1 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 214 records from Woodland Survey. 183 records from Eufáusidos norte de Chile. 5 records from Sycacantha Diakonoff, 1959 from China, with the descriptions of three new species (Lepidoptera: Tortricidae: Olethreutinae). 18 records from Happywhale - White-beaked Dolphin in Arctic Ocean. 3332 records from HBRG Other Invertebrates Dataset. 10 records from Cyanobacteria of Algal Collection of Soil Science Institute (ACSSI). 2 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 4 records from A new cryptic species of Scorpiops Peters, 1861 (Scorpiones: Scorpiopidae) from the northern Western Ghats, India. 22 records from Five new and five known species of the genus Tylencholaimus de Man, 1876 (Nematoda: Dorylaimida: Tylencholaimoidea) from Western Ghats of India. 882 records from AMAPPS Southeast Aerial Cruise Spring 2017. 275 records from Taxon occurrence data for the FungalRoot database. 2047 records from MCP-Anfibios - Coleção de Anfíbios. 95 records from Fauna herpetológica de los Parques Ecológicos Distritales Humedales Bogotá, D.C.. 7 records from Deep into darkness: the first stygobitic species of freshwater shrimp of the genus Caridina (Crustacea: Decapoda: Atyidae) from Northern Vietnam. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 6 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 123 records from Colección de referencia para Polen en 10 remanentes de bosque seco tropical en el Valle del Cauca. 2 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 3 records from A new species of Setodes Rambur (Trichoptera: Leptoceridae) from northern Michigan, USA. 340 records from Royal Belgian Institute of Natural Sciences Echinodermata collection. 450 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 3 records from Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae Nemesiidae) in Thailand. 8 records from Eight new species of marine dolichopodid flies of Thinophilus Wahlberg, 1844 (Diptera: Dolichopodidae) from peninsular Thailand. 1 records from Finnish Floristic Database (Literature Sources). 173 records from SEWBReC Algae and allied species (South East Wales). 2 records from Two new freshwater species of Bacillaria (Bacillariophyta) from Dongting Lake, China. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae Oxyporinae) in Yunnan Province, China. 33821103 records from iNaturalist Research-grade Observations. 566 records from SEFSC GoMMAPPS 2018 Fall Aerial Survey. 1 records from Lysimachia rupestris F. H. Chen & C. M. Hu (Primulaceae): a new record for the flora of Vietnam and reconsideration of its taxonomical position. 9 records from Two new species of the Amphinemura sinensis group (Plecoptera: Nemouridae) from southern China. 242 records from Revision of the cricket genus Nisitrus Saussure (Orthoptera: Gryllidae: Eneopterinae) and descriptions of five new species. 4 records from The Anagyrus (Hymenoptera: Encyrtidae) parasitoids of the obscure mealybug Pseudococcus viburni (Hemiptera: Pseudococcidae) in Spain, with description of a new species. 144 records from Données du/de la naturaliste zeitouni kevin provenant de la base de donnée du SINP Île-de-France CETTIA. 72 records from Registros asociados al proyecto: Ensayos de mantenimiento y reproducción en cautiverio de la medusa Lychnorhiza. 1 records from First data on the bionomics of Leptochilus (Euleptochilus) limbiferus (Morawitz 1867) (Hymenoptera: Vespidae: Eumeninae), with taxonomic notes and new records. 13950 records from SD - SD Herbarium, San Diego Natural History Museum. 9 records from MCCC - Mendocino College Coast Center Herbarium. 7 records from New species and new behavioral data of Phlugiola Karny, 1907 (Orthoptera: Tettigoniidae: Meconematinae) from the Brazilian Amazonian Rainforest. 3 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 3 records from Four new species of the genus Draconarius Ovtchinnikov, 1999 (Araneae, Agelenidae) from the Tibetan Plateau, China. 217 records from HBRG Badger Dataset. 79 records from Cumbria Non Native Invasive Species. 1 records from Anew species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from the Tapajós basin, Brazil. 13 records from Inventaire et suivi de la faune écrasée. 971124 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 40 records from Artrópodos plaga en yuca (Manihot esculenta) asociados al proyecto: Identificación de genes relacionados con mecanismos de resistencia contra plagas. 1000 records from nsmk_mm_2019. 1 records from A new species of the genus Rhachotropis from off Amamioshima Island northwestern Pacific (Crustacea: Amphipoda: Eusiridae). 4197 records from Vegetation of Rybachy Peninsula and Srendny Peninsula, Murmansk Oblast, Russia. 1 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 65 records from SNH Invertebrate Site Condition Monitoring 2015: Mount Bog SSSI. 20736 records from Observations.be - Orthoptera occurrences in Wallonia, Belgium. 8 records from DAR AVH data. 8 records from Happywhale - Commerson's Dolphin in South Atlantic Ocean. 43 records from Plan d'aménagement Forêt de Claye-Souilly. 11867 records from England Non Native Species records 1965 to 2017. 1 records from A new endemic species of Willowsia from Florida (USA) and descriptive notes on all New World Willowsia (Collembola: Entomobryidae). 3512 records from NEON Biorepository Mosquito Collection (Bulk Identified). 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 224 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 48 records from Garrapatas (Acari: Ixodidae) de zonas ganaderas del Magdalena medio de Antioquia. 1 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 1608 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 696 records from Abundances and biological traits of the juveniles lamprey sampled in the survey of lamprey abundance Indice on the Scorff river (France). 155 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 3 records from Happywhale - Southern Right Whale in South Pacific Ocean. 195 records from Pedestrian mammals census in W National Park. 58 records from Auckland Museum NZ Marine Collection. 915 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 4 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 58 records from Thrips (Thysanoptera) in Norway. 1 records from A new short brown unpatterned moray eel Gymnothorax andamanensis (Muraenidae: Muraeninae) from Andaman waters, India. 5 records from A key to species of genus Malcus Stål, with descriptions of four new species from China (Hemiptera: Heteroptera: Malcidae). 1 records from Two new species of cave-dwelling Charinus Simon, 1892 from Brazil (Arachnida: Amblypygi: Charinidae). 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 4 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1226 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Peces San cristóbal). 1109 records from Data collected on Mesosphaerum suaveolens, Mesosphaerum Pectinatum, Hyptis spicigera and Hyptis lanceolata. 198 records from Chronicle of Nature - Phenology of Plants of State Environmental Institution National Park Braslav lakes. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 4 records from Study of the genus Meleonoma Meyrick, 1914 (Lepidoptera: Autostichidae) from China, with descriptions of twenty-one new species (II). 3 records from UWIZM Turtles and Crocodilians. 623 records from Caracterización del caracol pala Lobatus gigas en la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 122 records from BIOTOPE_2017_12_18. 6 records from Studies on neotropical Phasmatodea XVII: Revision of Phantasca Redtenbacher, 1906, with the descriptions of six new species (Phasmatodea: Diapheromeridae: Diapheromerinae). 540 records from Distribution géographique de quelques espèces invasives du Bénin (Afrique de l'Ouest).. 7 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 6 records from Taxonomic revision of the species of Stenothemus from Southwest China (Coleoptera, Cantharidae), with the descriptions of five new species. 1 records from A new species of Hetereleotris (Teleostei: Gobiidae) from the Socotra Archipelago (north-western Indian Ocean), a rare case of a hole-associated adaptation in gobiid fishes. 2 records from Revision of the Melanogaster jaroslavensis group (Diptera: Syrphidae), with description of a new species from Afghanistan. 652 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Occurrences of Compsus auricephalus (Insecta: Coleoptera: Curculionidae) from some entomological collections Jun 29 2020. 1 records from Two new Cambodian semi-aquatic earthworms in the genus Glyphidrilus Horst, 1889 (Oligochaeta, Almidae), based on morphological and molecular data. 3946 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 3 records from Contribution to the knowledge of subterranean ground beetles from eastern Wuling Mountains, China (Coleoptera: Carabidae: Trechinae). 14257 records from Inventaire de la flore du PNRLG 2016 (Gironde). 214 records from Caracterización de briófitos en troncos en descomposición en el Parque Natural Chicaque con aplicabilidad a los procesos de conservación ex situ en el Jardín Botánico de Bogotá. 1089 records from Jeu de données convention Eurovia-SPN-2012-2016. 1 records from A survey on poorly known rainforest litter-dwelling spiders of Orchid Island (Lanyu, Taiwan) with the description of a new species (Araneae: Linyphiidae Tetrablemmidae, and Theridiosomatidae). 139 records from UVM Milkweed Pollinator Project. 81 records from Données du/de la naturaliste SENECAL Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 4068 records from Données d'observateurs divers (observateurs transmettant un nombre de données peu élevé) saisies dans Cettia-idf. 16232 records from Herbario Amazónico Colombiano. 122 records from Avifauna asociada a la parcela de investigación de la estación Tutunendo, Quibdó, Chocó. 2020. 57 records from NCSM Non-molluscan Invertebrates Collection. 19 records from New distributional records for ants and the evaluation of ant species richness and endemism patterns in Mexico. 4218 records from Inner Oslofjorden Phytoplankton Database. 6 records from One new species of the genus Ischnothyreus Simon, 1893 and re-description of I. yueluensis Yin & Wang, 1984 from China (Araneae, Oonopidae). 7 records from Six new species of the spider genus Centroctenus Mello-Leitão from the Neotropical region (Ctenidae, Cteninae). 1571 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 1 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 1 records from Database about reference specimens for medicinal plants, in the Apocynaceae family, owned by CNARP. 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 187 records from Colecção Entomológica do Museu de História Natural de Maputo. 3 records from Unesconia coibensis, gen. et sp. nov., a miniature sponge-associated shrimp from a biodiversity hotspot in the tropical eastern Pacific (Decapoda: Palaemonidae). 7 records from Colección de Microalgas Marinas de la Universidad del Magdalena. 1 records from New species and occurrence records of Japanese Solasteridae and Ganeriidae including a new species of Paralophaster from the North Pacific with an overview of Hyalinothrix. 2737 records from McDonald-Podesta-Fortuin-Gandhi Orchid Bee Collection. 1 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 6 records from New data on the genus Domene (Coleoptera: Staphylinidae: Paederinae) of mainland China. 24461 records from IMOS Plankton Collection - AusCPR: Zooplankton Abundance. 1 records from Addition to the known long-horned beetle fauna of the Bolivian Andes: A new lycid-like species of Mimolaia Bates, 1885 (Coleoptera, Cerambycidae, Lamiinae, Caliini). 7989 records from OBI - Robert F. Hoover Herbarium, Cal Poly State University. 17 records from Collection Polychaeta - ZSRO. 19 records from On the microphthalmous Lathrobium Gravenhorst species of Turkey II. Two new species, a new synonymy, and an updated key to Turkish species (Coleoptera: Staphylinidae: Paederinae). 684 records from Aquatic vascular plants of the Middle Urals (Sverdlovsk region, Russian Federation). 1 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 2723 records from imr_mareano_rpsledge. 1 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 1 records from Extraordinary bees of the genus Lasioglossum Curtis, 1833 (Hymenoptera: Apoidea: Halictidae) from China. 3942 records from MSB Bird Collection (Arctos). 20 records from Happywhale - Sei Whale in South Pacific Ocean. 13 records from New and noteworthy species of Begonia (Begoniaceae) from Vietnam and Laos. 238 records from Mushrooms Flora of Nepal at National Herbarium and Plant Laboratories (KATH). 26 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 563 records from UFRN-Fungos - Herbário UFRN - Fungos. 795 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from Ant genus Strongylognathus (Hymenoptera, Formicidae) in Bulgaria: a preliminary review. 82 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran. 943 records from Epibenthos and demersal fish monitoring in function of dredge disposal monitoring in the Belgian part of the North Sea. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 18 records from Andrena cyanura Cockerell, a valid North American species. 3 records from Two new species of the genus Leeonychiurus Sun & Arbea, 2014 (Collembola: Onychiuridae) from Korea. 55 records from TRAS LA RUTA DE LAS TORTUGAS GOLFINAS EN LOS CABOS, BCS 2009-2018 !! (aggregated per 1-degree cell). 219 records from CG04_2017_12_18. 25 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 261 records from Monitoreo de aves por medio de transectos libres en el Parque Nacional Natural Cueva de los Guácharos en el 2019. 156 records from The South American spider genera Mesabolivar and Carapoia (Araneae, Pholcidae): new species and a framework for redrawing generic limits. 641 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 2300 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 7 records from Happywhale - Sperm Whale in South Atlantic Ocean. 11918 records from Denver Museum of Nature & Science - Entomology. 228 records from FBIP: Identification of polychaetes used as bait. 2333 records from Insecta of Costa Rica (INBio). 5 records from A review of the Barbatula loaches (Teleostei: Nemacheilidae) from north-eastern China, with the description of four new species. 8927 records from Database for alien invasive plants occurrences in Germany. 1 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 2 records from A pilot phylogeny study of Nemobiinae inferred from 18 S, 28 S and genes, with descriptions of two new genera and a new species from Hainan, China (Orthoptera: Grylloidea: Trigonidiidae). 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 13 records from New and rare micro-pagurid hermit crabs (Crustacea: Anomura: Paguridae) from the Caribbean Sea and Gulf of Mexico. 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 17 records from Abejas corbiculadas (Apidae) en el marco del proyecto Comparación morfológica de los Cuerpos Fungiformes en abejas. 1 records from Description of a new species of deep-sea spider crab from the genus Crocydocinus Lee, Richer de Forges & Ng, 2019, from the south-eastern Arabian Sea (Crustacea Decapoda: Majoidea: Epialtidae). 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 480 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 49 records from University of Michigan Museum of Zoology, Division of Insects. 1 records from A remarkable new species of the genus Lepisiota Santschi (Hymenoptera: Formicidae) from Oman and the United Arab Emirates with a key to the Arabian species. 1 records from Three new species of Entomobrya from Poland (Collembola, Entomobryidae). 1 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 408 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 5 records from Two new Colombian harvestmen of the genus Quindina Roewer, 1914 (Opiliones Nomoclastidae). 2685 records from Données de la structure Pie verte bio provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from First description of the last instar larva and pupa of the aquatic crane fly Limnorimarga limonioides (Alexander, 1945) (Diptera: Limoniidae). 10 records from Collection Ichthyologie - SNSD. 6 records from Taxonomic revision of the Colombian Tityus (Archaeotityus) (Scorpiones, Buthidae) species: a morphological and morphometric approach, with a description of a new species. 479 records from Desarrollo de estudios ambientales dentro de las investigaciones para el futuro aprovechamiento hidroeléctrico del río Nare. 18 records from Seasearch Pink Sea Fan, Eunicella verrucosa, Survey. 2 records from Yunnan-Guizhou Plateau: a mycological hotspot. 2 records from Leptagrion itabaiana sp. nov. (Odonata: Coenagrionidae) from Serra de Itabaiana National Park, Sergipe state, Northeastern Brazil. 1 records from A new species of Leiochrides Augener, 1914 (Annelida: Capitellidae) from the Beibu Gulf, South China Sea. 60 records from Fish species observations from a monitoring survey of two Lake Victoria affluent rivers (Rivers Kagera and Sio). 1 records from Review of the Oriental genus Neoperlops Banks, 1939 (Plecoptera: Perlidae). 947 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidráulica de Calima. 2018. 36 records from BIOMEO_2017_12_18. 8 records from Untangling the trees: Revision of the Calumma nasutum complex (Squamata: Chamaeleonidae). 51 records from Distribution of aquatic beetles from the east of Morocco (Coleoptera, Polyphaga). 83 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 18351 records from Inventaire de la flore de Charente-Maritime 2015. 8 records from Contribution to the knowledge of Carabidae in Iran with the descriptions of five new taxa, proposing of four synonyms and providing of nine new records (Insecta: Coleoptera). 1 records from A taxonomic note of Pterocephalus (Caprifoliaceae) from N Iran. 158 records from Lochaber wild boar/feral pig camera trap survey, 2015. 3 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 14 records from Troides butterfly specimens at Museum Zoologi Bogor, Indonesia. 10372 records from DMNS Bird Collection (Arctos). 3917 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, February - December 2019. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 915 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 15 records from New sponge species from Seno Magdalena, Puyuhuapi Fjord and Jacaf Canal (Chile). 329264 records from Biome of Australia Soil Environments. 4727 records from Zooplankton Species Distribution and Abundance Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise, August 2017. 24 records from Happywhale - Crabeater Seal in Southern Ocean. 3 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 48635 records from Inventaire de la flore de Dordogne 2018. 12 records from Urban Barcode Project - Fungi. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 4752 records from Natural England bat roost visit records from 2013 onwards. 6057 records from 2018_nsmk_biodiversity_pi. 87 records from ACT and Southern Tablelands Weed Spotter. 4 records from Taxonomic review of the ant genus Dilobocondyla from China (Hymenoptera: Formicidae), with a revised key to the known species. 2090 records from NEON Biorepository Terrestrial Plant Collection (Belowground Biomass [Standard Sampling]). 616 records from Naturalis Biodiversity Center (NL) - Aves. 41017 records from National Stag Beetle Surveys (Great Stag Hunts). 136 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 2 records from A new species of the genus Pseudocrangonyx (Crustacea: Amphipoda Pseudocrangonyctidae) from Simbok Cave, Korea. 3 records from Dispatch from the field II: the mystery of the red and blue Opadometa male (Araneae, Tetragnathidae, Opadometa sarawakensis). 1 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 4 records from Données naturalistes de Monsieur LEFEBVRE François. 12 records from University of Manitoba (WIN) - Lichen Collection. 1 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 72 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 29 records from Données de la collection d'herbiers de Nouvelle-Calédonie du MNHN. 2 records from Cinetorhynchus gabonensis, a new species of hinge-beak shrimp (Crustacea: Decapoda: Rhynchocinetidae) from the eastern Atlantic. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 579 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 1 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 7121 records from Herbarium of Taiwan Forestry Research Institute. 945 records from Inventario de Aves Mámbita. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 17528 records from UK Cranefly Recording Scheme - records verified via iRecord. 2 records from Swiss National Diplopoda Databank. 10 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 2 records from First record of Pulvinaria urbicola Cockerell (Hemiptera: Coccidae) from India, with a key to the Indian species of Pulvinaria Targioni Tozzetti. 1 records from A new species of the genus Aalatettix Zheng & Mao (Orthoptera, Tetrigoidea Tetrigidae) from China. 16735 records from Données naturalistes de Damien AVRIL. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 2560 records from 1915-2016 Department for Environment Food & Rural Affairs (Defra), Marine Strategy Framework Directive (MSFD) Collation of invasive non-indigenous species. 1 records from A new species of the Amolops monticola group (Anura: Ranidae) from southwestern Yunnan, China. 9 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 2 records from blindsnakes. 5770 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 12 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 60 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 26 records from Carabidae of the European North-East of Russia. 2 records from A new species of the genus Ancylocheles Haig, 1978 (Crustacea: Decapoda: Anomura: Porcellanidae) from Gujarat, northwestern India. 1 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 3984 records from FBIP: Diversities of microbiomes from South African arid and natural soils. 76 records from Données naturalistes de Severine GUYOT. 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyacá. 8 records from Noble Chafer: Post-BAP records from 1998 onwards. 1 records from Revision of the world Apenesia Westwood (Hymenoptera, Bethylidae). 692 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 1 records from Contribution to the Glolarnaca Gorochov, 2008 (Orthoptera: Gryllacrididae: Hyperbaeninae) from China. 2225 records from Données naturalistes d'Anaïs MAS. 63 records from RISC Non-Native Species Records for Muntjac. 20 records from The harvestmen fauna (Arachnida: Opiliones) of the Katunsky Biosphere Reserve and adjacent territories (South Siberia, Russia), with a description of a new species of Sabacon (Sabaconidae) and notes on Sabacon sergeidedicatum Martens, 1989. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 1 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 39 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 173 records from Tejidos de árboles del bosque seco tropical de Colombia que cuentan con muestra de semillas. 7 records from Happywhale - Sperm Whale in Arctic Ocean. 14389 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 206 records from Geelong Field Naturalists Club. 2 records from New species of black corals (Cnidaria: Anthozoa: Antipatharia) from deep- sea seamounts and ridges in the North Pacific. 100 records from Données d'observation d'écrevisses exotiques envahissantes en Haut de France et Normandie sur la période 2014 à 2018. 262 records from Freshwater fish records via iRecord - additional species. 3846 records from Ichthyology Collection - Royal Ontario Museum. 518 records from Escarabajos coprófagos en ecosistemas agropecuarios de la quebrada Piedra Candela, en la altillanura plana del Meta. 141 records from Données du/de la naturaliste Angé christofer provenant de la base de donnée du SINP Île-de-France CETTIA. 455 records from Línea base del medio biótico en los bosques para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguablanca -El Morro Yopal. 483 records from Tejidos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 7 records from Two new species of Atopophlebia Flowers, 1980 (Ephemeroptera, Leptophlebiidae) from Colombia. 3 records from Euscorpius thracicus sp n (Scorpiones: Euscorpiidae) from Bulgaria. 16 records from Riodinid butterfly specimens at Museum Zoologi Bogor, Indonesia. 20 records from New data on the genus Cheilosia Meigen (Diptera, Syrphidae) from Central Asia with descriptions of two new species and a key to the ‘ group C’. 1781 records from Caracterización ecológica y de la diversidad en los ecosistemas de arrecifes de coral y pastos marinos en la jurisdicción marina de CORPAMAG, departamento del Magdalena, Caribe Colombiano. 1342 records from Gunma Museum of Natural History, Fungi Specimen. 1546 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 1 records from Apennocoris pilosulus: rediscovery of a forgotten big-eyed bug taxon from New Caledonia (Heteroptera: Lygaeoidea: Geocoridae). 374 records from AMAPPS Northeast Aerial Cruise Winter 2017. 40 records from Flora Sumatra: Digitizing and data basing specimens of the Sumatran Flora deposited at Herbarium Universitas Andalas (ANDA)-Part 2. 235 records from Учет ондатры. 4 records from Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from Pakistan. 1 records from Anemone pindariensis sp. nov., a new species from Pindari valley of the Western Himalaya, India. 7 records from Genus Salix in SVER Herbarium. 1 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura Diogenidae) from shallow coastal waters in Japan. 4057 records from Données naturalistes de David HAPPE. 4801 records from Spiders of the Udmurt Republic, Russia. 19 records from SANBI: Mozambique Sky Islands-Reptile Survey. 5 records from A taxonomic review of the genus Dicranorhina Shuckard (Hymenoptera: Crabronidae: Crabroninae) from the Indian subcontinent with the description of three new species from Southern Western Ghats. 67 records from The distribution of Pteris fauriei group. 3 records from Two new orthoclad species from Colombian Andes (Diptera: Chironomidae). 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 2758 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 33 records from The Smicridea (Smicridea) fasciatella species group (Trichoptera: Hydropsychidae) in Brazil: six new species and new distributional records. 2 records from A second species of the genus Blythia Theobald, 1868 (Squamata: Colubridae) from Mizoram, India. 230 records from Données de la structure CORIF/LPO-idf provenant de la base de donnée du SINP Île-de-France CETTIA. 71 records from Evaluación de la diversidad biológica y las relaciones tróficas de las charcas estacionales del norte de La Guajira. 60 records from A revision of the shield-back katydid genus Neduba (Orthoptera: Tettigoniidae: Tettigoniinae: Nedubini). 3 records from Racekiela andina sp. nov. (Spongillida: Spongillidae): first report of a freshwater sponge from the Venezuelan Andes. 1 records from Taxonomic review of the Hyphessobrycon panamensis species-group (Characiformes: Characidae). 19400 records from EDP Foz Tua: Bat Roosts - Ecological & Compensatory Measures Monitoring Programs [2011-2017]. 4615 records from Meetnetten.be - Transects for dragonflies in Flanders, Belgium. 3312 records from Estudio de la comunidad zooplanctónica y fitoplanctónica en los ecosistemas de arrecifes coralinos mesofóticos del Parque Nacional Corales de Profundidad. 543 records from Cyanobacteria from freshwater lakes in the Azores Archipelago, Portugal. 5 records from A new species of Chimarra from China (Trichoptera, Philopotamidae) with description of its larva. 185 records from Mapeo de Theobroma cacao usando sistemas de información geográfica, para optimizar la producción de cacao en Colombia. 15 records from Inventaire et suivi de la Cistude d’Europe sur le site Natura 2000 ‘Zones humides de Moliets, La Prade et Moisans’ (FR7200718). 58 records from University of Nebraska State Museum Fish Collection. 7 records from Société_du_Canal_de_Provence_2017_12_18. 459 records from IASTracker. Invasive Alien Species database. 4052 records from EFC - Herbário Escola de Florestas Curitiba. 1 records from A new genus and species of sand-hopper, Mauritiorchestia fayetta gen. nov., sp. nov (Amphipoda, Talitridae) from Mauritius. 2 records from A new species of the “ apacheanus ” group of genus Pseudouroctonus from western Texas (Scorpiones: Vaejovidae). 24283 records from Swiss National Databank of Mayflies, Stoneflies and Caddiesflies. 1 records from plasmopara_sphagneticolae. 39 records from Nineteen new species of Alycaeidae from Myanmar and Thailand (Gastropoda: Caenogastropoda: Cyclophoroidea). 531 records from Données acquises entre fin 2014 et 2016 dans le cadre du plan de gestion de la tourbière de Passeben. 1 records from On the subgenus Eurysunius Reitter of Turkey VI. Two new species from Sivas province in central northern Anatolia, with a key to Turkish species (Coleoptera: Staphylinidae: Paederinae, Astenus). 1350 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 2909 records from Fishes of INEP and NFH collections. 4 records from Polyzosteria cockroaches in Tasmania (Blattodea: Blattidae: Polyzosteriinae) represent a new, endemic species, with allopatric alpine and coastal sub-populations. 12 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 140761 records from Swiss National Fungi Databank. 1319 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Liste des récoltes par Herbier de dépôt TOGO. 976 records from Données naturalistes de PISZCZAN thierry. 3177 records from Insect collection, UiT, University Museum (TSZ). Insect labeling project and PhD-duty-work. 1 records from Systematics of Guajirolus ektrapeloglossa Flowers 1985 (Ephemeroptera: Baetidae). 35 records from Status and spatial diversity of Sorghum wild species in Malawi.. 73 records from Magnoliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 6 records from Estudio etnobotánico de las cactáceas en las comunidades rurales de Cucaita, Ráquira y Villa de Leyva (Boyacá). 1 records from Happywhale - Sei Whale in Southern Ocean. 11 records from Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination. 10 records from A new genus and species of Sternaspidae (Annelida: Polychaeta) from the deep eastern Atlantic. 2 records from Descriptionoftwonew speciesofDinetus Panzer, 1806 (Hymenoptera: Crabronidae Dinetinae) with key to species. 40283 records from Meetnetten.be - Transects for butterflies in Flanders, Belgium. 2283 records from SER Site-based Surveys. 1 records from Taxonomic revision of the genus Elmomorphus Sharp, 1888 I. Japanese and Korean species (Coleoptera: Dryopidae). 398 records from Invasive, neolimnetic and aboriginal fish species in Dnipro, Danube and Southern Buh basins (Ukraine, 2021). 1844 records from FASFC - Exotic vector and pathogen surveillance programme in Belgium - Mosquitoes & Culicoides. 1656 records from Oskarshamn herbarium (OHN). 81050 records from Observations Regelink Ecology and Landscape. 2 records from Redescription of Ryukyua circularis (Pillai, 1954) (Isopoda, Cymothoidae), parasite of the Bleeker smoothbelly sardinella Amblygaster clupeoides Bleeker, 1849 from India. 120 records from Rwanda's wetlands biodiversity data from different inventories that were conducted between year 2008 and 2017. 1 records from First record of Petrobia (Petrobia) pseudotetranychina (Trombidiformes: Tetranychidae) in Asia, with two new host plants for Tetranychidae from Iran. 141 records from Michael Barkla's Observations. 180 records from Acoustic detections from R/V Song of the Whale during the winter 2019 MAPS survey (NMFS permit 14809). 3062 records from Vascular plant specimens of National Museum of Nature and Science (TNS). 704 records from The ground beetles (Caraboidea) of Southern Sikhote-Alin. 12 records from Description of Titanoeca deltshevi sp. n. from Bulgaria with faunistic notes on related species in the Balkans (Araneae, Titanoecidae). 89 records from Microbes in drinking water and biofilms (18S rDNA amplicon study). 5 records from A survey of East Palaearctic Gnaphosidae (Araneae). 10. Three new Gnaphosa species from the Dzhungarian Alatau Mountains (Eastern Kazakhstan). 31869 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 177 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 229 records from Algae collection, Oslo (O) UiO. 9 records from New genera, species and occurrence records of Goniasteridae (Asteroidea; Echinodermata) from the Indian Ocean. 377 records from Données du/de la naturaliste delzons olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 21420 records from Baikalsky State Nature Biosphere Reserve and its buffer zone: floristic data. 23 records from An update to the taxonomy and distribution of the Arabian Tapinoma Foerster, 1850 (Hymenoptera: Formicidae) with an illustrated key and remarks on habitats. 6 records from The Nearctic species of Grzegorzekia Edwards (Diptera: Mycetophilidae). 11 records from Chronicle of Nature - Phenology of Mammals of Tigirek State Nature Reserve. 467 records from Jeu de données convention CD78-Service du patrimoine naturel-2014-2015. 10 records from Diversity of intertidal, epibiotic, and fouling barnacles (Cirripedia, Thoracica) from Gujarat, northwest India. 714 records from Données naturalistes de Jean-Paul LECHAPT. 19 records from Insect specimens of Kushiro City Museum. 2 records from Cerogobius petrophilus (Perciformes: Gobiidae), a new gobiid genus and species from the Red Sea. 2 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 61 records from Herpetos del cerro Iró, municipio del río Iró, Chocó. 2020. 1126 records from Sciomyzidae Recording Scheme. 4363 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 2562 records from Northern Ireland Environmental Recorders - Marine Species Records. 167 records from Eco-Stratégie_2017_12_18. 2026 records from Inventaire et dénombrement des oiseaux du Parc Naturel Communautaire de la Vallée du Sitatunga au Sud Bénin. 2 records from A new species and new records of minuta - group Gnamptogenys from Brazil (Hymenoptera: Formicidae). 391 records from Fauna y flora en las cercanías del gasoducto que alimenta la mina de Ferroníquel Cerro Matoso S.A.. 1 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 6 records from TRAS LA RUTA DE LAS TORTUGAS MARINAS EN COZUMEL !!! (aggregated per 1-degree cell). 70 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Horèwendou) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1296 records from Comptage Wetlands en Essonne. 4525 records from 成龍溼地鳥類生態紀錄. 59 records from Données du/de la naturaliste Sarouille Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 74 records from UNCW JAX Aerial Survey -Left side- 2017. 450097 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 3 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 1438 records from OUPR - Herbário "Professor José Badini". 87126 records from CEDaR Online Recording. 221 records from Colección de Asterales del Museo Botánico CORD. 7 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 7 records from Brentidae Acratini du massif du Mitaraka, en Guyane: une synthèse des données (Insecta, Coleoptera, Curculionoidea). 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 3 records from Hiding in plain sight on Gunung Muria: A new species and first record of rock gecko (Cnemaspis Strauch, 1887; Squamata, Gekkonidae) from Java, Indonesia. 460 records from Données naturalistes de Delphine MONTAGNE. 960 records from Occurrence database of bryophytes and native animals of southern Chile. 60 records from Revision of the spider genus Stygopholcus (Araneae, Pholcidae), endemic to the Balkan Peninsula. 469 records from Phenology of Iridaceae. 1 records from A new species of ‘ Bird’s Nest’Anthurium sect. Pachyneurium (Araceae) from Brazil. 194 records from The InBIO Barcoding Initiative Database: Diptera 01. 1 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 54823 records from Physical and biological data collected along the Texas, Louisiana, Mississippi, Alabama, and Florida Gulf coasts in the Gulf of Mexico as part of the Harmful Algal BloomS Observing System. 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 1 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 46 records from Syndicat_Mixte_de_Défense_des_Berges_de_l'Asse_2017_12_18. 14 records from Amoeboid protists isolated from ancient Siberian permafrost. 301 records from Comunidad de hormigas en la Orinoquia Colombiana: estructura en tiempo y espacio. 92 records from Historical findings of Salvinia natans in Ukraine. 2164 records from Collembola in subarctic peatlands. 2 records from Distribution extension of Calotes irawadi Zug, Brown, Schulte & Vindum, 2006, previously confused with C. versicolor (Daudin, 1802): first record from China. 86 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 74 records from Données espèces - Expertise IPE 69. 12 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes Heptapteridae) from the Sierra Nevada de Santa Marta, Colombia. 1 records from Two new species of the genus Apsidophora Diakonoff, 1973 (Lepidoptera Tortricidae: Olethreutinae) from Thailand. 286 records from Riqueza y distribución de briófitos reófilos en el predio Golconda, ubicado en el municipio de Hato, Santander. 2 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Aves (MG-ZV-A). 2094 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 911 records from Flora vascular de Torca, Localidad de Usaquén (Bogotá - Colombia). 6 records from Happywhale - Southern Elephant Seal in Southern Ocean. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 651 records from Insectos asociados a cultivos de Albahaca y Ají en Santa Marta. 916765 records from Estonian Ornithological Society (BirdLife Estonia). 73 records from Fauna marina de la costa vasca - Sistema de Información de la Naturaleza de Euskadi. 3763 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 1 records from Happywhale - Minke Whale in South Pacific Ocean. 144 records from Inventaires complémentaires du Fort d'Aubervilliers (93). 31179 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 1898 records from Registros biológicos Parcela permanente HATOVIAL SAS en Barbosa, Antioquia. 5342 records from SBC LTER Darwin Core Archive: Kelp Forest Reef Fish Abundance. 139 records from Données du/de la naturaliste Bergemer Jean-Denis provenant de la base de donnée du SINP Île-de-France CETTIA. 18341 records from Weevil and Bark Beetle records via iRecord. 320 records from Caracterización hidrogeológica para el diagnóstico ambiental de alternativas del proyecto hidroeléctrico San Bartolomé (ISAGEN y HMV).. 1 records from A new southern record of the holopelagic annelid Poeobius meseres Heath, 1930 (Flabelligeridae). 2520 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 536 records from NEW-1. 2 records from New records of brittle stars (Echinodermata: Ophiuroidea) from the Lakshadweep atolls, northern Indian Ocean, with notes on Indophioderma ganapatii Sastry Marimuthu & Rajan, 2019. 11990 records from Phytocenoteca of the laboratory of ecosystem theory (Plants). 251 records from Sperm morphology of 264 songbird species. 120 records from Tejidos asociados al estado de conservación y riesgo de extinción del ensamblaje de anfibios de tres páramos colombianos. 23 records from Wichita State University Collection. 3 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 1 records from A new species and new records of Malagasy Megalopinus Eichelbaum (Coleoptera Staphylinidae, Megalopsidiinae), with notes on the sperm pump in rove beetles. 10 records from Four new species of the spider genus Cicurina Menge, 1871 from China (Araneae: Dictynidae). 2 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 5 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 2940 records from EDP Foz Tua Reptiles - Ecological Monitoring Program [2011-2017]. 1 records from Eudraces barclayi sp. nov., with some notes on the genus Eudraces Marshall (Coleoptera: Curculionidae: Entiminae: Myorhinini). 535 records from NEW-2. 4 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 17 records from Three new widely distributed and polymorphic species of Amynthas earthworms (Oligochaeta, Clitellata, Megascolecidae) from South China. 12 records from New Psocoptera (Hexapoda, Insecta) records from Belarus. 7 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 4 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 15124 records from Diversidade e ocorrência de peixes em Inhambane (2009-2017). 13 records from Bohemannia auriciliella (Nepticulidae) specimen data. 12 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 1 records from Description of a new species of Lutosa Walker, 1869 (Orthoptera: Anostostomatidae: Lutosinae) from the Brazilian Atlantic Forest, with biological and behavioral information. 1 records from Happywhale - Short-beaked Common Dolphin in South Pacific Ocean. 5 records from données aranéologiques de ROLLARD Christine. 2 records from Horned and spiky: Tegotettix derijei sp. n. (Orthoptera: Tetrigidae) is a peculiar new pygmy grasshopper species from Mindanao. 15062 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 19893 records from Atlas of Life in the Coastal Wilderness. 486 records from Gipuzkoako Foru Aldundiaren Landareen Germoplama Bankua / Banco de Germoplasma Vegetal de la Diputación Foral de Gipuzkoa. 6 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 16 records from Genética de la Conservación del Oso Andino en el Parque Nacional Natural Cordillera de los Picachos y área de amortiguación. 43 records from Happywhale - Blue Whale in North Atlantic Ocean. 2 records from Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China. 516 records from Marine algal flora of Flores and Corvo Islands, Azores. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 39 records from Amphibia collection of the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 10 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 446 records from Insectivorous Bats of Gunung Mulu National Park, Malaysia. 269 records from données arachnologiques de CARR David. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 40 records from Données du naturaliste Julien Schwartz. 65 records from HUEFS herbarium - Universidade Estadual de Feira de Santana - Herbário Virtual REFLORA. 1 records from Belarima violacea (Lucas, 1847) (Coleoptera, Chrysomelidae), a new genus and species for the European fauna. 1412 records from Mamíferos asociados a un bosque húmedo tropical de Barrancabermeja, Santander. 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 990 records from Bacterial communities from Thrombolites of Lake Sarmiento. 4 records from Contribution to the knowledge of the cavernicolous beetle genus Aspidaphaenops Uéno from Guizhou (Coleoptera: Carabidae: Trechinae). 385 records from University of British Columbia - Spencer Entomological Collection (UBCZ). 6752 records from Dragonfly Ireland 2019 to 2024. 10 records from Two new freshwater crab species of the genus Nanhaipotamon Bott, 1968 (Crustacea, Decapoda, Potamidae) from Huizhou, Guangdong Province, southern China. 120 records from Herbário da Pontifícia Universidade Católica do Paraná - HUCP. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 2 records from A new species of day gecko (Reptilia, Gekkonidae, Cnemaspis Strauch, 1887) from Sri Lanka with an updated ND 2 gene phylogeny of Sri Lankan and Indian species. 3 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 2 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 5 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 1 records from A systematic review of Rhinopetitia Géry (Teleostei, Characiformes, Characidae) with descriptions of four new species and redescription of R. myersi Géry. 13 records from New species and distribution records for Mexican and Central American Cerambycidae (Coleoptera). 1 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 4 records from The Muscidae (Diptera) of Armenia. 46 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 41 records from NEON Biorepository Aquatic Plant, Bryophyte, Lichen and Macroalgae Collection (Herbarium Vouchers [Standard Sampling]). 65 records from Données du naturaliste Arnaud Bak. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 19 records from Large Branchiopoda occurrence data in the Northern Western Ghats, India. 213 records from JCT AVH data. 63 records from University of Tennessee Bryophyte Herbarium. 29 records from CRC HRC PMRF Small Vessel-Based Monitoring Surveys February 2016. 65 records from UNCW JAX Aerial Survey -Right side- 2017. 264 records from Nature-type mapping in Norway (Viken) 2020. 1 records from A new species of the Goblin Spider genus Predatoroonops Brescovit, Rheims & Ott 2012 (Araneae, Dysderoidea: Oonopidae), with new records for the genus. 70 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 125 records from Registros de anuros presentes en los Páramos de Santurbán, Rabanal y Las Hermosas. 95 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 1 records from A new species of Hemiphyllodactylus (Squamata: Gekkonidae) from Hong Kong. 4 records from The pseudodichotomous Dasya sylviae sp. nov. (Delesseriaceae, Ceramiales) from 60 - 90 m mesophotic reefs off Bermuda. 927 records from Invertebrados marinos asociados a ecosistemas de manglar en Buenaventura, Valle del Cauca. EPA-IIAP 2019. 37 records from Happywhale - Fin Whale in South Atlantic Ocean. 1 records from Collection Myriapoda - SNSD. 299 records from DBRC Hemiptera species records 1969 to 2015. 3 records from Mountainous millipedes in Vietnam. I. Two new species of the family Paradoxosomatidae from Mount Fansipan (Diplopoda, Polydesmida). 187 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 867 records from Data on animal species in the Biosphere Reserve of W Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 1120 records from Diversity of Amphibians in the Tshopo and Bas-Uélé provinces of the Democratic Republic of the Congo. 2 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 1941 records from Bryophyte Herbarium, Oslo (O) UiO. 2 records from A new large-bodied, rupicolous Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) allied to Cnemaspis heteropholis Bauer, 2002 from the Central Western Ghats of Karnataka, India. 458 records from Anfibios y Reptiles del Centro Universitario Regional Noreste (UdelaR). 1719 records from RECORD Butterfly Data. 8 records from The InBIO Barcoding Initiative Database: Portuguese Snakeflies (Raphidioptera). 3 records from Urogymnus acanthobothrium sp. nov., a new euryhaline whipray (Myliobatiformes: Dasyatidae) from Australia and Papua New Guinea. 1183 records from Aves en fincas ganaderas sostenibles del Meta. 4181 records from Camera trapping bird data. 3 records from A new species of rock-dwelling Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Tamil Nadu, southern India. 109 records from Happywhale - Minke Whale in North Atlantic Ocean. 5 records from Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin. 1 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from coastal hills in Cha-am, peninsular Thailand. 4614 records from Distribution and abundance of different bat species in the interior of Arabuko-Sokoke Forest and adjacent farmlands in Gede, Kilifi County, Kenya. 24 records from Happywhale - Sperm Whale in South Pacific Ocean. 196 records from Données naturalistes de DESMOTS Didier. 3 records from Happywhale - Steller Sea Lion in North Pacific Ocean. 17 records from New species of Hemerodromia Meigen (Diptera: Empididae: Hemerodromiinae) associated with limestone karstic waters in Thailand. 630 records from Relevé floristique dans les bassins du fleuve Niger à Faranah (BID-AF2015-0066-REG). 1110 records from Insect (Lepidoptera) Biodiversity Across Forest Canopy and Understorey in SE-Asia BIFA5_026. 15 records from Chronicle of Nature - Phenology of Birds of FGBU National Park Kenozersky. 385 records from Biodiversidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 6 records from Taxonomic studies on the genus Orancistrocerus van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 2651 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 63 records from Plumularioid hydroids (Cnidaria: Hydrozoa) from off New Caledonia collected during KANACONO and KANADEEP expeditions of the French Tropical Deep-Sea Benthos Program. 84 records from Macroinvertebrados de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 10 records from Some soil-inhabiting mites (Acari: Mesostigmata) from Kazakhstan, with description of a new species of Gaeolaelaps Evans & Till (Acari: Laelapidae). 15 records from Additions to the knowledge of Manota Williston (Diptera: Mycetophilidae) from the Neotropical region, with description of four new species. 1 records from Amphicnemis rigiketit sp. nov. from Sarawak, with notes on Amphicnemis remiger Laidlaw, 1912 (Odonata: Zygoptera: Coenagrionidae). 13 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 3338 records from Collembola in the soil of different forest formations in protected areas of Moscow and the Moscow region. 2 records from A new species and new record of the genus Platybaetis Müller-Liebenau, 1980 (Ephemeroptera: Baetidae) from Eastern Himalaya, India. 53 records from Avistamiento de fauna marina desde la embarcación en la Expedición de Montes Submarinos 2021. 22 records from Collection of Animal Cell Culture. 141 records from Importancia del Parque Estatal Cerro de la Tortuga para la conservación de los mamíferos del estado de Morelos, México. 16 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 282 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 1 records from A new endemic species of Acanthocereus (Cactaceae) from southern Jalisco, Mexico. 16 records from Avistamiento de Aves Corregimientos de Juanchaco y Ladrilleros, Buenaventura, Valle del Cauca - Septiembre 2016. 2 records from Données naturalistes de Willy CHENEAU. 4172 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 2 records from Chronicle of Nature - Phenology of Mushrooms of FGBU National Park Kenozersky. 2 records from A new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from Yunnan, China and its phylogenetic relationship to other congeners. 1 records from Phegopteris excelsior (Thelypteridaceae): A New Species of North American Tetraploid Beech Fern. 3553 records from Florida Manatee Synoptic Aerial Survey 1991-2019. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 3 records from Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia. 20179 records from Welsh Invertebrate Database (WID). 1 records from A new species of Polypedates Tschudi, 1838 (Amphibia: Anura: Rhacophoridae) from West Bengal State, Eastern India. 363 records from Fototrampeo de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 5 records from Three new species of the pandalid shrimp genus Pandalopsis Spence Bate, 1888 (Crustacea: Decapoda: Caridea) from the southwestern Sea of Okhotsk, with supplemental note on P. glabra Kobjakova, 1936. 135 records from Données naturalistes de Monsieur PRESSE Tony. 1 records from The eastern Pacific species of Salmoneus Holthuis, 1955, with description of a remarkable new species from Las Perlas Archipelago, Panama (Malacostraca: Decapoda: Alpheidae). 448 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 9606 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 9 records from Morphological and phylogenetic study of five species of Astrocystis and Collodiscula on bamboo. 2 records from First record of the family Stephanidae (Hymenoptera: Stephanoidea) for the fauna of Saudi Arabia, with the description of a new species. 1 records from Meschia zoui sp. nov., first representative of the family Meschiidae from China (Hemiptera: Heteroptera: Lygaeoidea). 8 records from Genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) from Laos, with descriptions of five new species. 203 records from Museu Paraense Emilio Goeldi - Lepidoptera Collection. 29438 records from Long-Term Monitoring Network Vegetation Quadrats. 2 records from The ant genus Myopias Roger, 1861 (Hymenoptera: Formicidae: Ponerinae) in Thailand, with descriptions of three new species. 2535 records from Bell Museum plants. 122 records from Ictiofauna asociada a fuentes hídricas presentes en la parcela de investigación estación Tutunendo, Quibdó, Chocó. 2020. 2075 records from Données naturalistes de Pierre FRAPA. 3 records from New species and records of Awas Löbl (Coleoptera: Staphylinidae: Pselaphinae) from China, with notes on the biology of the genus. 2 records from Two new species of Flintiella Angrisano 1995 (Trichoptera: Hydroptilidae Stactobiini) from northern Brazil. 4 records from Hap
Keywords: GBIF; biodiversity; species occurrences